From embryo to sexual maturity: chronic BPA exposure under elevated contamination scenarios induces multi-organ toxicity in marine medaka (Oryzias melastigma) - Yangmei Li; Zhang Huan; Qin Lin; Junyi Liu; Wenyang Xiao; Ning Zhang; Zailiang Li; Yanping Zhang; Yusong Guo; Zhongduo Wang; Zhongdian Dong (Marine Pollution Bulletin, 2026)

Numerical analysis of downwash airflow distribution from multi-rotor UAV in soybean-maize strip intercropping canopy - Xinghua Liu; Lei Yang; Yang Li; Zhi Li; Fan Jiang; Yanping Tian; Xiang-Dong Li (Biosystems Engineering, 2026)

Diagnosing critical gaps in urban wastewater systems in China to inform policy priorities - Ranbin Liu; Yundi Deng; Yanping Qiao (Utilities Policy, 2026)

Effects of mixed-culture fermentation on bioactive compounds, antioxidant capacity, and flavor metabolomics of red sour soup - Yuke Liu; Yanping Cui; Lan Cheng; Yingying Wang; Yan Ding; Shuhong Ye (International Journal of Food Microbiology, 2026)

Pressure-mediated mechanosensitive Piezo2 channel is activated in neurogenic bladder and promote bladder fibrosis in children - Lei Lv; Yanping Zhang; Qi Li; Junkui Wang; Shuai Yang; Zhaokai Zhou; Shuai Li; Zhengguang Zhang; He Zhang; Xingchen Liu; Yibo Wen; Jian Guo Wen (Journal of Molecular Medicine, 2026)

Optimization and research on variable load control methods for supercritical carbon dioxide Brayton Cycles - Xiuting Liu; Yanping Huang; Yuan Zhou; Houjun Gong; Yu Tang; Minyun Liu (Annals of Nuclear Energy, 2026)

Soil quality evolution and constraints in newly reclaimed farmland from gully consolidation in Yuanmou dry-hot valley of Southwest China - Yangqing Luo; Yifan Dong; Yanping Liu; Yingze Wang; Xingwu Duan (Soil and Tillage Research, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Numerical investigation on the flow field characteristics and the effect of column boot clearance angle on hydrodynamic performance of deep-draft cylindrical offshore platforms - Chengming Qin; Zhe Chen; Yanping He; Yadong Liu (Ocean Engineering, 2026)

Selective recovery of nickel from spent FCC catalysts using a bio-electrochemical coupled system: The synergistic role of organic acids and Eh-pH regulation - Daoqing Liu; Qianwei Li; Hao Liu; Yanping Zhu; Chunmao Chen (Journal of Environmental Chemical Engineering, 2026)

Effects of stir-fried Hemp (Cannabis sativa L.) seed polysaccharides on blood deficiency syndrome in rats based on metabolomics and gut microbiota. - Minghao Sun; Haipeng Tang; Chenxi Bai; Qian Wang; Meng Liu; Yanping Sun; Qiuhong Wang; Haixue Kuang (Food Research International, 2026)

Potential of biofortification with tissue-adhesive exopolysaccharide-producing Lactiplantibacillus plantarum to fine-tune microstructure, stabilize texture and color, and enrich flavor of radish Paocai during fermentation - Yuli Huang; Haimei Lai; Yali Wang; Jiaqi Liu; Mengting Liu; Yanping He; Lihong Ge; Nan Zhao (Food Bioscience, 2026)

Long-term PFOA and cadmium Co-contamination alters soil carbon, nitrogen, and phosphorus cycling: Insights from metagenomics and metabolomics - Yanping Cai; Beihai Zhou; Shuming Liu; Chuyu Shang; Baoguo Yang; Yunqing Liu; Shengguang Zhang; Ruixue Fan; Waseem Hassan; Rongfang Yuan; Huilun Chen (Environmental Research, 2026)

Energy window-guided molecular adsorbent for highly selective cesium capture: Breaking the Rb+/Cs+ separation bottleneck - Yanping Wang; Dezhen Fang; Kexin Li; Xiushen Ye; Wenjie Han; Pengrui Zhang; Zhijian Wu; Guosheng Shi; Haining Liu (Chemical Engineering Journal, 2026)

Unveiling microbial sulfate reduction in Acid Mine Drainage Treatment using a Chained Environmental-Microbial machine learning approach - Yanping Deng; Beiyi Xiong; Hao Chen; Yongyang Wang; Xin Liu; Chuling Guo; Zhi Dang (Chemical Engineering Journal, 2026)

An integrated experimental and computational study on a COX-2-targeted AIE probe for precise cancer cell imaging via restriction of intramolecular rotation - Jianxi Liu; Shengfa Song; Yonglin Zhang; Jiale Hu; Shulin Chen; Lulu Zhu; Li Shen; Zhen Sun; Ying Xue; Hao Jiang; Wei Ji; Jinmei Sun; et al. (Analytica Chimica Acta, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Salinity reduces cadmium bioavailability and toxicity in the Oryzias melastigma: Evidence from fish exposure and cell-based ion-competition assays - Zhongdian Dong; Jinghua Wang; Haozhong Tian; Jiahao Gao; Yue Liu; Nengneng Ding; Yiqing Yuan; Guohua Zhu; Xiaomin Zhao; Zailiang Li; Ning Zhang; Yanping Zhang; et al. (Marine Pollution Bulletin, 2026)

Measuring and enhancing urban water supply resilience: A dynamic coupling framework and its application in Beijing - Yanping Liu; Jiahua Wei; Minglei Hou; Jiaqi Xu; Chenfei Yan; Li Xue (Sustainable Cities and Society, 2026)

Upcycling waste glass into chitosan-modified zeolite for heavy metal immobilization and deep mineralization: A "waste-treats-waste" paradigm - Xinxin Li; Rongxin Guo; Zhihan Zhang; Yifeng Zou; Ziyi Yang; Dexun Zou; Yanping Liu (Process Safety and Environmental Protection, 2026)

Anthropogenic dominance of water storage variability in the Yellow River Basin: A machine learning synthesis of multi-source data (1981–2031) - Yanping Cao; Zunyi Xie; Dandan Liu; Chaolin Mu; Jielun Wang; Yihao Chang; Yingjun Pang (Journal of Hydrology, 2026)

Corrigendum to “Spatiotemporal prediction of PM2.5 concentration over the Beijing–Tianjin–Hebei region based on forecasting, interpolation, and correction of ERA5 precipitable water vapor” [J. Atmos. Sol. Terr. Phys. 285 (2026), Article 106859] - Xiangshun Meng; Yanping Liu; Yong Wang; Chunhong Liu; Wei Du; Yingliang Wang (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Valorizing jackfruit shell into a hydrothermal liquid seed-priming agent for salinity-stressed crops - Tao Zhang; Yanping Zhu; Yongle Yu; Keyi Zhang; Pan Zhao; Xiaomeng Han; Weigang Wang; Shihu Shu; Dandan Ke; Xiuping Zhan; Xiaoshuang Han; Jiping Shi; et al. (Bioresource Technology Reports, 2026)

Pomelo polysaccharides: A review of the extraction techniques, purification, structural characteristics, interactions, biological activities, applications and future prospects - Jingwei Wang; Ting Yang; Kaiyang Liu; Yuesong Xiao; Xiaoming Wang; Haixue Kuang; Yanping Sun (Trends in Food Science & Technology, 2026)

Cyromazine induces neurotoxicity associated with damage to dopamine, serotonin, glutamate, and GABA neuronal systems through reactive oxygen species (ROS) generation in Caenorhabditis elegans - Zibo Yin; Jusong Liu; Qianmei Pang; Yunfei Zhang; Lanying Wang; Yanping Luo (Pesticide Biochemistry and Physiology, 2026)

Parametric investigation of roll damping for a polar icebreaker using CFD and free-decay experiments - Wei Zhang; Yadong Liu; Yanping He; Chengming Hao; Hanyi Yao; Houfei Wu (Ocean Engineering, 2026)

Enhancement of microbial protein production via hydrogen oxidizing bacteria in microbial electrolytic protein-production cell system - Rui Dong; Hangyu Sun; Yilin Jiang; Haotian Liu; Yue Wang; Xingjia Fu; Yanping Liu; Ziyi Yang (Journal of Environmental Chemical Engineering, 2026)

Aliovalent Mg2+ doping in CdIn2S4 activates sulfur vacancies and promotes p-p orbital hybridization to enhance photocatalytic CO2 reduction - Yi Liu; Raotong Wen; Zuofang Yao; Bing Leng; Zebin Yu; Hongxiang Zhu; Yikai Wang; Xinqiu Tan; Yanping Hou; Shuangfei Wang (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal prediction of PM2.5 concentration over the Beijing–Tianjin–Hebei region based on forecasting, interpolation, and correction of ERA5 precipitable water vapor - Xiangshun Meng; Yanping Liu; Yong Wang; Chunhong Liu; Wei Du; Yingliang Wang (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Fabrication of RuCo bimetallic catalyst enabling efficient hydrogen generation via ammonia borane hydrolysis - Xianyun Liu; Lu Zhao; Han Wu; Linyan Bian; Yanping Fan; Baozhong Liu (Fuel, 2026)

Toward precise layer control of chemical vapor deposition growth of graphene films: from graphene to graphite - Runhan Xiao; Yangjian Xu; Chuang Tian; Jiawen Liu; Jie Cheng; Yanping Sui; Zhiying Chen; Shujie Tang; Guanghui Yu (Chemical Engineering Journal, 2026)

GmHMGR6 enhances salt stress tolerance in soybean through modulation of nitrogen metabolism - Xinjie Feng; Hongzhen Liu; Yingyue Zhang; Yanping Li; Zhengxing Guo; Rong Bao; Xiuli Zhang; Xinying Liu; Huihui Zhang (Plant Cell Reports, 2026)

Salvianolic Acid A Relieves Acute Lung Injury by Promoting the Expression of FOXO1 and Activating Autophagy Through the Inhibition of miR-217-5p - Xia Liu; Yanping Shi; Li Huang; Hongbo Chen; Raofei Fan; Hongzhong Zhang; Qiaofen Li; Na Yan; Maiding He; Yonghua Yang (Biochemical Genetics, 2026)

RAD23A promotes multiple myeloma cell survival through DNA damage response, proteostasis and enhanced metabolic activity - Hongxiu Liu; Yihua Wang; Xunru Liu; Ni Yang; Senxin Wang; Jie Zhao; Yaqi Shi; Huichao Wang; Yanping Ma (Toxicology and Applied Pharmacology, 2026)

Ethylene responsive transcription factors alleviate browning in fresh in-hull walnut (Juglans regia. L) by modulating GABA metabolism under controlled atmosphere storage - Niu Ye; Guoli Dai; Shizhe Liu; Yongqi Zhang; Shan Liu; Sike Wang; Yuwei Wang; Yuanlin Gou; Ting Zhang; Yanping Ma; Qinggang Zhu; Huiling Ma (Postharvest Biology and Technology, 2026)

Multi-level predictive group maintenance optimization method for multi-component systems: Subsea Christmas tree as a case - Yanping Zhang; Baoping Cai; Chuntan Gao; Chenyushu Wang; Yiliu Liu (Ocean Engineering, 2026)

Nitrogen doping engineering of Ru nanoparticles/Mo2C MXene for efficient hydrogen production via NH3BH3 hydrolysis - Zhenluo Yuan; Fei Ya; Yang Shi; Shuyan Guan; Pingping Wang; Pei Liu; Shiqian Zhao; Qiuming Peng; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

Single-nucleus RNA sequencing reveals a spatiotemporal pattern of H2S signaling in Chinese cabbage - Jiao Zhang; Yang Chen; Bo Liu; Yuwei Qin; Yue Luan; He Yin; Wenqi Liu; Limei Chen; Jixian Zhai; Yanxi Pei; Yanping Long; Zhuping Jin (Science China Life Sciences, 2026)

Assessment of Heavy Metal Pollution in Cultivated Soils and Rice Grains on the South Bank of Taihu Lake, China - Yanping Shi; Yiping Chen; Jiajia Ren; Juntao Zhao; Dan Liu (Bulletin of Environmental Contamination and Toxicology, 2026)

Application of POD-ANN reduced order model to fluid-thermal-structural coupling analysis in printed circuit heat exchangers - Hanxing Liu; Minyun Liu; Shenghui Liu; Yu Tang; Ruilong Liu; Junjie Fei; Yuanfeng Zan; Ruohan Zheng; Yanping Huang (Annals of Nuclear Energy, 2026)

The PorV protein as a cross-protective antigen against Riemerella anatipestifer infection - Sen Li; Yanhua Wang; Xiong Liu; Keke Ren; Yanping Deng; Yuncai Xiao; Sishun Hu; Zili Li; Hongbo Zhou; Zhengfei Liu; Zutao Zhou (Veterinary Microbiology, 2026)

A multi-scale assessment of the water–energy–pollution nexus in Sri Lanka’s industrial parks - Yanping Wang; Jingru Liu; Chinthaka Kularathne; Xiuzhi Hua; Shashini Yapa (Resources, Conservation and Recycling, 2026)

Decline of beneficial microbes and proliferation of latent pathogens: Key drivers of postharvest disease in citrus - Jianghua Chen; Mengting Xu; Ting Zhu; Ziyi Yang; Juan Liu; Jie Duan; Yang Lin; Xiao Yu; Daohong Jiang; Yanping Fu (Postharvest Biology and Technology, 2026)

Environmentally relevant phthalate esters mixture disrupts gut-brain axis homeostasis in Apis cerana with Glu/GABA-Gln-related neurochemical imbalance - Jian Liu; Siwei Wang; Yanping Liu; Xiaonan Wang (Journal of Environmental Sciences, 2026)

Integrative metabolomic and transcriptomic analyses reveal coordinated variation in phenolic acid metabolism and redox-related traits in Ocimum basilicum accessions - Jingtian Yang; Zhengqiao Liao; Jialin Li; Mei Liu; Yanping Mao; Guoyu Yang; Lei Liu (Planta, 2026)

A Study on the Species Diversity, Mating Types, and Clinical Relevance of Trichophyton mentagrophytes/interdigitale Complex Infections in Guizhou Province - Wei Hu; Kexin Xu; Jing Zhou; Wanglan Luo; Songgan Jia; Xiangyu Liu; Zhengling Shang; Yinhui Jiang; Zhi Liu; Yanping Jiang (Mycopathologia, 2026)

Heat transfer and dynamic behavior of wall-adhered carbon dioxide droplets: power-law correlation and the cryogenic ring effect - Qifan Wang; Minyun Liu; Yanping Huang; Shanfang Huang; Ruohan Zheng; Houjun Gong (Annals of Nuclear Energy, 2026)

Non-invasive Computational Techniques for Diagnosing Myocardial Ischemia: Challenges and Future of FFRCT/iFRCT - Bao Li; Jincheng Liu; Yang Yang; Hao Sun; Chi Zhu; Leo Hwa Liang; Zijie Wang; Luyao Fan; Suqin Huang; Xueke Li; Guangfei Li; Liyuan Zhang; et al. (Annals of Biomedical Engineering, 2026)

Narirutin Mitigates Dextran Sodium Sulfate-Induced Enteritis in Procambarus clarkii by Modulating Intestinal Microbiota - Jian Li; Yitian Chen; Yanping Cai; Huiling Zhang; Bin Qiu; Xingfei Huang; Yan Wen; Aimin Wang; Bin He; Yude Wang; Shaojun Liu (Fishes, 2026)
Enteritis is a disease that affects Procambarus clarkii, significantly impacting aquaculture due to its high incidence and mortality rates, resulting in economic losses. Currently, the molecular mechanisms behind enteritis in Procambarus clarkii are not well understood. In this study, we established a model of intestinal inflammation induced by dextran sodium sulfate (DSS). Subsequently, histopathological changes, transcriptome analysis, intestinal microbiota analysis and immunofluorescence analysis were conducted. Histopathology showed that after treatment in the DSS + Narirutin (NR) group, there was an improvement in intestinal inflammation, and the structure of the intestinal tissue was partially restored. The intestinal transcriptome analysis revealed that in the DSS + NR group, 234 genes were upregulated and 188 genes were downregulated after treatment. This indicates a significant change in gene expression. KEGG enrichment analysis revealed that the DEGs were significantly enriched in TGF-β signaling pathway and PI3K-Akt signaling pathway. The results from 16S rRNA sequencing showed that in the DSS + NR group, the relative abundance of Akkermansia muciniphila significantly increased. Immunofluorescence results showed that, compared to the control group, the expressions of Occludin, nuclear factor-kB-p65 (NfkB-p65), Zonula occludens-1 (ZO-1), and Claudin-1 decreased following DSS treatment. However, treatment with NR was able to inhibit these changes. This further validated that NR can alleviate enteritis in Procambarus clarkii.

Harnessing molecularly imprinted polymers for multiplex detection of emerging contaminants in foods: advances and future perspectives - Quanbin Fu; Yanping Pei; Wenming Liu; Xin Sun; Peng Wu; Houshen Li; Shiyun Ai (Critical Reviews in Food Science and Nutrition, 2026)

Water temperature affects pathogenicity of ranavirus to adult bullfrogs - Yanping Ma; Le Hao; Xi Liang; Gang Wang; Zhenxing Liu (Aquaculture, 2026)

Optimal management of co-location marine activities in three-dimensional space: A Stackelberg game-based framework - Shuo Wang; Jiaju Lin; Chao Liu; Yanping Li; Saiya Xu (Ocean & Coastal Management, 2026)

High pH decreases the contents of stable organic nitrogen fractions and nitrogen supply capacity by inhibiting soil organic carbon in saline-sodic paddy fields - Baishun Liu; Lihua Huang; Fengyi Zhang; Jinghui Cai; Lei Tian; Xiaotong Jiang; Yanping Liang; Ge Zhu; Guangzhi Huang (Soil and Tillage Research, 2026)

Recyclable standardized sludge for performance evaluation of low-temperature drying units: Preparation and feasibility verification - Yuting Qin; Yanping Guo; Yongyou Hu; Jingyu Liu; Guanying Huang; Guanghuan Li; Haochun Chen; Qingying Huang (Journal of Environmental Management, 2026)

Molecular dynamics simulation of polyamide based reverse osmosis for boron removal - Yawei Du; Mengru Cui; Jingxin Wei; Yanping Li; Yize Liu; Shizhao Wang; Zhiyong Ji (Desalination, 2026)

Zwitterionic nanoparticle-mediated interfacial hydration for robust, salt-rejecting, and anti-fouling solar steam generation - Jianbin Zhang; Yuhao Zhai; Zhichao Chen; Ting Lv; Dianming Li; Yanhua Liu; Yanping Wang; Wufang Yang; Baoli Ou; Libang Feng; Feng Zhou (Chemical Engineering Journal, 2026)

Enhancing wildfire spread scale prediction with explainable AI: a hist gradient boosting and SHAP-based approach - Bin Liao; Tao Zhou; Jiong Yu; Yanping Liu; Tao Zhang; Tiantian Lu (Natural Hazards, 2026)

Analysis of the blowdown of supercritical carbon dioxide from simple vessel - Fengyuan Tian; Minyun Liu; Yanping Huang; Ruohan Zheng; Yangle Wang; Houjun Gong; Yu Tang; Tianzeng Liu; Jinghan Hu; Haohan Yuan; Yuan Zhou (Annals of Nuclear Energy, 2026)

Silymarin sensitizes human colorectal cancer cells to 5-ALA–mediated photodynamic therapy by enhancing cytotoxicity and apoptotic signaling in vitro - JingJing Zhao; Ying Liu; YanPing Zhang; Qin Jiang (DARU Journal of Pharmaceutical Sciences, 2026)

Evolution of carbon sink patterns and spatial planning suitability in the Qingdao Coastal Zone based on the coupled InVEST–PLUS model - Chunxia Xu; Chunjuan Wang; Dahai Liu; Zhiwei Zhang; Yanping Li; Zheng Li (Frontiers in Marine Science, 2026)
To support the “dual-carbon” strategy and develop a carbon-sink-oriented coastal spatial planning framework, this study applies the coupled InVEST–PLUS model to Qingdao using 30 m resolution land-use data. Six spatial drivers (DEM, slope, GDP, population, road, and water proximity) are used to simulate land-use change and evaluate its impact on carbon storage. Model validation results indicate that the PLUS model shows good performance (Kappa ≈ 0.79, FoM = 0.168). The results indicate that (1) during 2010–2020, land-use patterns in the study area changed markedly, characterized by a decrease in farmland and an expansion of architecture area, while forest increased slightly and overall ecological land declined. (2) Total carbon storage dropped from 5.3174 × 10 7 t (2010) to 5.2749 × 10 7 t (2020), with a net loss of 4.25 × 10 5 t. Spatially, carbon storage showed a “clustered-high, contiguous-medium, radial-low” pattern. (3) DEM and water proximity primarily drove the expansion of farmland, forest, grassland, and waters, while population density and DEM dominated architecture growth; bare land expansion was mainly driven by population. Based on these findings, carbon storage transfer pathways are quantified, providing a scientific basis for low-carbon-oriented territorial spatial governance in coastal zones.

Sequential multi-objective maintenance optimization with dynamic importance ranking: A case study of subsea transportation system - Yixin Zhao; Baoping Cai; Yiliu Liu; Yanping Zhang; Shibo Wu; Gan Li (Ocean Engineering, 2026)

Safe-critical formation reconfiguration of unmanned surface vehicles using closest collision point measurements - Lu Liu; Jiaxing Zhou; Yanping Xu; Zhouhua Peng (Ocean Engineering, 2026)

AutoML democratizes water quality forecasting: Lowering expertise barriers - Yangyang Chu; Yun Fang; Liangzhi Sun; Yang Zhang; Liujian Wang; XiaoMeng Han; Mou Lv; Haixing Liu; Kunlun Xin; Weigang Wang; Yanping Zhu; Shihu Shu (Journal of Water Process Engineering, 2026)

Photoelectrotrophic denitrification and iron-sulfur-nitrogen cycle enhance nutrient removal in pyrite-amended constructed wetlands - Xiaoxiao Hou; Lingyun Mu; Yingying Liu; Yanping Xiao; Xinshan Song; Xiaoxiang Zhao; Dong An (Journal of Environmental Management, 2026)

Insight into the oxidation mechanism of low-salt Sichuan-style sausages treated with inclusion complexes of tea-polyphenol/β-cyclodextrin/NaCl and electron beam irradiation using machine learning algorithms - Ya Liu; Jiuhong Du; Wenyi Ran; Lihui Huang; Wenyue Yu; Huan Guo; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Hong Gao (Food Chemistry, 2026)

Climate-sensitive environmental drivers shaping epipelagic and mesopelagic fauna biodiversity patterns in the Amundsen–Bellingshausen Seas, Southern Ocean - Jiayu Fan; Yang Liu; Yanping Luo; Yuru Li; Mi Duan; Chunlin Liu; Zhenjiang Ye; Jianchao Li; Peng Sun; Chi Zhang; Jun Zhao; Jianfeng He; et al. (Environmental Research, 2026)

A simplified RUBY reporter-enabled hairy-root system for rapid evaluation of genome editing and gene function in grapevine - Chong Ren; Yanping Lin; Mohamed Salaheldin Mokhtar Mohamed; Chencong Liu; Zhenchang Liang (Planta, 2026)

Integrated morphological, transcriptomic, and metabolomic profiling reveals differential development mechanisms in two weeping forsythia genotypes during tissue culture - Yanxia He; Yanping Zheng; Jiaqi Geng; Yue Wang; Na Qi; Xu Lu; Xiaoxiao Wang; Yongjin Sun; Helong Wen; Xiaoya Liu; Xin Sun; Xianping Wang; et al. (Physiology and Molecular Biology of Plants, 2026)

Non-Invasive functional assessment of severity in cerebral arterial stenosis using cerebral flow fraction: A hemodynamic study - Hao Sun; Bao Li; Zijie Wang; Liyuan Zhang; Jun Zhao; Yanping Zhang; Guangfei Li; Jinli Ding; Yanjun Gong; Hwa Liang Leo; Youjun Liu (Medical & Biological Engineering & Computing, 2026)

Railway CORS GNSS PWV forecasting using normal time-frequency transform and deep learning with transfer learning strategy - Chen Chang; Yanping Liu; Yong Wang; Yunlong Zhang; Xiangshun Meng; Haozhe Chi; Chunrui He (Advances in Space Research, 2026)

The atmospheric residual error model of time-series InSAR based on ERA-5 PWV in Beijing, China - Haozhe Chi; Yong Wang; Yunlong Zhang; Chengwu Yang; Chen Chang; Fei Qiao; Xiangshun Meng; Chunhong Liu; Yanping Liu (Advances in Space Research, 2026)

Numerical Study on the Effect of Column Boot Diameter-to-Height Ratio on the Hydrodynamic Performance of Deep-Draft Cylindrical Offshore Platforms - Chengming Qin; Zhe Chen; Yanping He; Yadong Liu (Journal of Marine Science and Engineering, 2026)
For deep-draft cylindrical platforms with a large annular column boot, the influence of the column boot diameter-to-height ratio (d/h) on motion performance remains unclear. This study investigates the effect of d/h on platform hydrodynamics while keeping the main body geometry, displacement, and draft unchanged. A hybrid numerical model validated against tests is adopted: STAR-CCM+ free-decay simulations identify equivalent linear damping, and ANSYS AQWA predicts hydrodynamic coefficients, response amplitude operators, and coupled time-domain responses under a 100-year survival sea state in the western South China Sea. Increasing d/h substantially increases heave added mass and added pitch moment of inertia, leading to longer natural periods and higher damping in heave and pitch. However, its effect on motion responses is non-monotonic and strongly response-dependent. As d/h increases, the responses are initially reduced markedly. The minimum surge and heave responses occur at d/h = 2.39 and 4.67, with reductions of about 34.0% and 87.2%, respectively, while the pitch response is already reduced by about 67.3% at d/h = 7.22. Further increases in d/h may weaken surge and heave mitigation while providing limited additional benefit for pitch. These findings provide qualitative understanding and quantitative guidance for response-oriented column boot design and optimization of similar platforms.

Inhibition of potato common scab by Bacillus subtilis XT11 and its reshaping of the microbial community in potato geocaulosphere soil - Ning Liu; Minghao Lv; Yongdong Wang; Huimin Ma; Wei Fan; Junjie Ma; Jiguang Wang; Yanping Gao; Jinbiao Ma; Bo Zhou; Wenchong Shi; Zheng Gao (World Journal of Microbiology and Biotechnology, 2026)

Structural equation modeling revealed optimized ridge-furrow configuration integrated with straw-soil crust enhancing carbon sequestration and sainfoin yield in semiarid agroecosystems - Abdul Qadeer; Qi Wang; Rizwan Azim; Xiaole Zhao; Wen Ma; Ibrahim Awuku; Fujia Li; Qinglin Liu; Yanping Liu; Bing Liu; Xuchun Li; Muhammad Sanaullah; et al. (Computers and Electronics in Agriculture, 2026)

A three-dimensional layered model for sea area usage across dimensions of space, functional elements, and time - Saiya Xu; Yanping Li; Qi Yue; Dahai Liu; Heng Hu; Shuo Wang; Yuqing Chen; Yilin Liu (Ocean & Coastal Management, 2026)

Local macrophage dynamics–inspired engineering of time-programmed nano-vaccine scaffold for postoperative cancer immunotherapy - Zhenyu Xu; Qian Chen; Mingyu Hao; Yiyang Cao; Xiaoqin Kuang; Chunjiayu Li; Zhihao Liu; Jiawen Xue; Jianing Zhao; Mengwei Zhao; Naicong Cai; Yiqing Li; et al. (Science Bulletin, 2026)

Microwave-assisted regeneration of CuxO-modified activated carbon saturated with sulfamethazine: Mechanism and performance evaluation - Yanping Liu; Zixiu Li; Dandan Liu; Mingjie Han; Jianfeng Gao; Haoyu Zou (Process Safety and Environmental Protection, 2026)

Preparation and characterization of gelatin/bacterial nanofibrillated cellulose composite membranes based on an ecological engineering strategy - Fengge Yu; Jieying Fan; Jialin Zhang; Xiangying Liu; Yue Meng; Yanping Chi; Zhiqiang Yang; Caiming Li; Hongrui Sun; Hua Zhang; Lining Kang (Food Hydrocolloids, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

Divergent responses of maize and soybean to intercropping: Insights from arbuscular mycorrhizal fungi diversity, colonization, and related-genes expression - Shihui Yu; Xinru Liu; Ling Liu; Yanping Ma; Baohong Liu; Wuyan Xiang; Ying Zhang; Peiyong Liu; Chen Feng; Caixia Sun (Plant and Soil, 2026)

Quasi-real-time retrieval of ERA5 precipitable water vapor over mainland China - Xiangshun Meng; Yong Wang; Yunlong Zhang; Wei Du; Yanping Liu; Xiao Liu (Advances in Space Research, 2026)

Bypassing Typhoons Cause Three-dimensional Dramatic Changes in Temperature and Ocean Heat Content of the Yellow Sea and Bohai Sea: A Case Study with Super Typhoon Maysak (2020) - Fangguo Zhai; Junyan Zhang; Yucheng Wang; Yujie Dong; Yanping Ma; Cong Liu; Zizhou Liu (Advances in Atmospheric Sciences, 2026)

Assessing Coastal Ecological Restoration Effectiveness in Qingdao Based on a Multi-Dimensional Entropy-Weighted TOPSIS Model - Chunxia Xu; Chunjuan Wang; Dahai Liu; Yanping Li; Chao Liu; Zheng Li (Journal of Marine Science and Engineering, 2026)
Coastal ecological restoration is a key approach to enhancing ecosystem resilience; however, the stage-wise evolution of restoration outcomes and the underlying driving mechanisms remain insufficiently quantified. Using Qingdao City as the study area, this research integrates remote sensing inversion, the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model, and time-series data from 2010 to 2020 to develop a comprehensive evaluation system for ecological restoration effectiveness, comprising 17 indicators across five dimensions: vegetation, biology, hydrology, economy, and climate. Based on this system, the entropy-weighted method is applied to conduct a dynamic assessment of restoration outcomes. The results indicate that (i) the composite evaluation score in the study area decreased from 0.36 in 2010 to 0.19 in 2015 and then increased to 0.74 in 2020, forming a “V-shaped” nonlinear trajectory with 2015 as a turning point, which is temporally consistent with a delayed response of ecological restoration outcomes following the implementation of major anthropogenic interventions. (ii) Dimension-specific analysis indicates that the decline in the composite score during 2010–2015 was mainly associated with the hydrological dimension, within which chemical oxygen demand (COD) and ammonia nitrogen emissions showed marked increases and were among the highest-weighted indicators. After 2015, following the intensive implementation of regional and system-oriented restoration projects such as the Blue Bay Initiative, pollutant emissions were observed to be effectively controlled, and Bare land area showed a continuous decline. These changes coincided with the rapid rebound of the composite score, within which Bare land area, as the highest-weighted indicator, played a prominent regulatory role. Marked differences were observed among dimensional responses: the biological and vegetation dimensions showed sustained improvement throughout the study period, whereas the hydrological dimension exhibited greater variability over time and stronger temporal alignment with policy-related phases. (iii) Robustness tests indicate that, after completely excluding climate-related variables, the composite score still increased from 0.36 and 0.24 to 0.77, with the “V-shaped” recovery pattern remaining unchanged. This result suggests that the observed improvement in restoration effectiveness in 2020 was more closely associated with systematic human interventions, rather than with short-term climatic fluctuations. This study provides a quantitative and transferable methodological framework for the dynamic evaluation and stage-oriented analysis of coastal ecological restoration effectiveness.

Macrobenthic community dynamics inform mangrove restoration practices for China - Yiyong Rao; Danyi Li; Fengxia Wu; Lizhe Cai; Shufei Zhang; Huaxue Liu; Yanping Zhong; Honghui Huang (Ocean & Coastal Management, 2026)

Sargassum-inspired multifunctional adsorbent by grafting cyanopyridine ionic liquid on down fiber: achieving integrated enhancement of adsorption selectivity and efficiency - Yanping Wang; Longfang Ren; Xinqing Han; Huaqing Liu; Bing Shi; Taotao Qiang (Water Research, 2026)

Long-distance lateral migration, accumulation and dissipation of natural gas in the northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Faqi He; Wei Zhang; Yanping Ma; Lihua Yang; Deyong Shao; Nan Du; Fuyu Chen (Gondwana Research, 2026)

High-resolution skin-like microlithographic displays for visual-tactile system - Baoying Sun; Xiaoli Zhao; Chuang Xue; Mingxin Zhang; Pengbo Xi; Guoqiang Ren; Hao Liu; Junru Zhang; Yanping Ni; Yanhong Tong; Liangwen Feng; Qingxin Tang; et al. (Chemical Engineering Journal, 2026)

Synthesis and biological evaluation of coumarin-based urea derivatives demonstrating apoptosis-inducing and anti-angiogenic properties for non-small cell lung cancer treatment - Zirui Chen; Qi Liao; Pengyu Zhao; Yuefei Geng; Jianguo Wen; Shu Liu; Yanping Tang; Chenjuan Zeng; Tingting Yan; Yongmei Shen; Funeng Geng (Medicinal Chemistry Research, 2026)

Experimental study on boiling heat transfer of water flowing in a mini zigzag tube - Yihang Wu; Tianzhou Xie; Shenghui Liu; Jianjun Xu; Shuangqing Chen; Xiaoliang Zhu; Yanping Huang; Muhammad Jahanzaib; Junlin Huang; Ruiying Gao (Annals of Nuclear Energy, 2026)

High-parameter multiphase critical flow in supercritical carbon dioxide nuclear energy system - Gengyuan Tian; Yuan Zhou; Yanping Huang; Yuan Yuan; Chengtian Zeng; Shuai Liu (Annals of Nuclear Energy, 2026)

Comammox Nitrospira dominates autotrophic nitrification in paddy fields under long-term fertilization - Bingjie Ren; Yanping Wang; Yuchao Wang; Yuling Yang; Zhenfa Su; Haikun Wu; Wangting Yang; Yuhan Jin; Jinghao Jin; Shuai Liu; Lidong Shen; Xu Zhao (Agriculture, Ecosystems & Environment, 2026)

Analysis of atmospheric residual error and construction of correction model for GACOS-Corrected PS+DS time-series InSAR based on ERA5 PWV - Fei Qiao; Yong Wang; Yunlong Zhang; Chen Chang; Haozhe Chi; Chunhong Liu; Xiangshun Meng; Yanping Liu; Chengwu Yang (International Journal of Remote Sensing, 2026)

The Evolution and Development of Integrated Coastal Zone Management in China Since the 1950s - Yanping Li; Wenjing Zheng; Tuanxi Dong; Yingzi Yang; Shuo Wang; Yinuo Kang; Yilin Liu; Yuqing Chen; Dahai Liu (Coastal Management, 2026)

Transcriptome analysis of possible genetic-level defects in the use of large-sized Chinese mitten crab ( Eriocheir sinensis ) parents for breeding - Fujun Xuan; Jinghao Hu; Lei Gao; Ruifang Wang; Yanping Yang; Ying Pan; Jun Zhou; Rongchen Liu (Invertebrate Reproduction & Development, 2026)

Improving slurry flow predictions in horizontal pipes: A modification to the Burns turbulent dispersion force model - Weihuang Liu; Yanping He; Mingzhi Li; Hongbo Zhu; Minmin Zheng (Ocean Engineering, 2026)

Exfoliation characteristics of tetrahydrofuran on surface-active structure of different coals and its inhibition effect on oxidation - Jun Guo; Yunfei Wu; Hu Wen; Yin Liu; Yongfei Jin; Changming Chen; Yanping Quan (Fuel, 2026)

One-step microwave fabrication of waste potato-derived bifunctional film: sustainable mulch-fertilizer for plastic substitution - Dongqing Cai; Weijia Liu; Dongfang Wang; Shihu Shu; Pan Zhao; Tao Zhang; Yi Qiao; Xiaoshuang Han; Weijian Zhang; Kaimin Zhu; Rongjun Zhang; Yanping Zhu (Environmental Research, 2026)

Grass roots on gully bed inhibit plunge pool development but have a limited influence on headcut retreat: a case study based on an in-situ experiment in dry-hot valley of southwest China - Yanping Liu; Yifan Dong; Jie Feng; Ronghua Zhong; Li Rong (CATENA, 2026)

Evaluation of salt tolerance in Agropyron Gaertn.: key indicators, optimal conditions, and implications for crop improvement - Jiarui Zou; Jing Yang; Ying Liu; Yanping Yang; Lai Wei; Haiming Han; Shenghui Zhou; Weihua Liu; Jinpeng Zhang; Lihui Li; Yonghe Che (Genetic Resources and Crop Evolution, 2026)

Split biosensor based on nano-enzymatic ferrocene-tyramine deposition reaction for detection of SMP30 antibody - Yanping Xing; Xixiang Xie; Jiangtao Liu; Tao Zhao; Xiyu Liu; Pan Wu; Faquan Lin; Yong Huang (Analytica Chimica Acta, 2026)

Unvegetated Tidal Flats: A Critical Yet Vulnerable Coastal Blue Carbon Sink - Yanping Wang; Changchun Li; Zhaoliang Peng; Jing Luo; Senlin Zhu; Yumeng Sun; Ruping Liu; Dongcheng Jiang; Xiangqian Zhou; Faming Wang (Global Change Biology, 2026)
Unvegetated tidal flats, despite accounting for approximately 24.9% of global blue carbon ecosystem area, remain underrepresented in blue carbon budgets. Here, we synthesize data from 184 sites across 23 countries to quantify their carbon stocks, carbon accumulation rate (CAR) and greenhouse gas (GHG, CO 2 and CH 4 ) emissions. Our results reveal that tidal flats sequester 8.6 (4.5–9.9) Tg C yr −1 and store 1.2 (0.7–2.0) Pg C in the top meter of sediments, increasing global blue carbon estimates by 6%–17%. However, they simultaneously emit 0.073 Tg CH 4 yr −1 (3.3 Tg CO 2 eq yr −1 ), 27.9% of the CH 4 emissions from salt marshes, offsetting 14.1% (1.8%–20.4%) of their carbon sequestration benefits. Mudflats exhibit the highest carbon stocks and CO 2 fluxes among different sediment types, primarily due to their abundant binding sites of fine‐grained particles and stronger microbial activities. Both CAR and CH 4 fluxes decline poleward, with tropical zone as hotspots. Our findings highlight the urgency of integrating tidal flats into climate mitigation strategies, particularly given their vulnerability to land‐use changes and sea‐level rise. Conservation efforts must balance carbon sequestration gains against CH 4 trade‐offs to optimize their climate regulation potential.

A Novel, Dual-Response Chemosensor Based on Ferrocene Derivative for the Selective Detection of Al3+ Ions : Fluorescence and Electrochemical Signaling - Wenqin Liu; Yanping Liu; Zenghui Li; Santai Zou; Pingnan Wan; Yan Lin (Journal of Fluorescence, 2025)

Chronological and geochemical constraints on the origin and timing of carbonate-cemented sandstones in the Middle Jurassic Zhiluo Formation, northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Yanping Ma; Lihua Yang; Nan Du (Marine and Petroleum Geology, 2025)

Improvement of electron transfer via anthraquinone-2-sulfonate addition to enhance volatile fatty acids production in anaerobic digestion system - Xiaoyue Li; Tingting Jiang; Huiyan Jing; Yue Cui; Yanping Liu; Ziyi Yang (Journal of Environmental Chemical Engineering, 2025)

Performance and mechanism of Co-MOF@BiVO4 sol-gel/graphite felt cathode for antibiotic degradation in heterogeneous electro-Fenton system - Jinghui Pan; Xi Li; Naif Abdullah Al-Dhabi; Zuofang Yao; Songyu Fan; Chenchen Xing; Yujia Liu; Hongxiang Zhu; Wangwang Tang; Yanping Hou (Journal of Environmental Chemical Engineering, 2025)

Research on hourly precipitation prediction along railways based on ERA5 reanalysis and post-processing correction - Xiangshun Meng; Yong Wang; Yunlong Zhang; Chengwu Yang; Chen Chang; Haozhe Chi; Yanping Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Study on the mechanism of influence of group extraction on low-temperature spontaneous combustion characteristics of lignite - Changming Chen; Jun Guo; Hu Wen; Yin Liu; Bo Gao; Yunfei Wu; Yanping Quan (Fuel, 2025)

Advances in acetylcholinesterase-based biosensing technologies for organophosphorus pesticide detection: A comprehensive review (2020–2024) - Qian Zhang; Jing Yu; Yanping Wei; Rong Yang; Jin Liu; Yangyang Su; Die Gao; Jing Zeng (Food Chemistry, 2025)

Revealing the polyphenol modulation mechanism for in vitro gastric digestion properties of myofibrillar proteins via noncovalent interaction - Yan Lu; Chaoqun Chen; Yu Chen; Shuaiqian Wang; Yanping Hu; Ping Liu; Hongbin Lin; Jie Tang; Jie Zhao (Food Chemistry, 2025)

Superior energy storage and charge-discharge performance achieved in (Pb1-3/2La )(Hf0.9Sn0.1)O3 antiferroelectric ceramics - Shuifeng Li; Xiaobin Guo; Zhenhua Tang; Xin-gui Tang; Qijun Sun; Yanping Jiang; Wenhua Li; Qiuxiang Liu (Chemical Engineering Journal, 2025)

Enhanced dehydrogenation kinetics and cyclic stability of NaAlH4 through nitrogen coupling with Ti3C2 MXene - Zhenluo Yuan; Ruyi Guo; Xiuxiu Zhang; Jiabao Cai; Haiwen Li; Qiuming Peng; Shumin Han; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2025)

Synthesis and antifungal activity of arecoline derivatives containing amino acid fragments - Xianwu Liu; Jianwen Zhang; Zefang Qin; Chengcheng Zhang; Huaxin Liu; Ting Zhou; Lanying Wang; Yanping Luo; Zhigang Zeng (Molecular Diversity, 2025)

P, N co-doped spherical graphitic carbon as metal-free peroxymonosulfate activator for diclofenac degradation: Non-radical pathway mechanism, performance and toxicity - Yanping Xiao; Jinping Mei; Haoqing Wang; Haobin Zhong; Qi Xu; Qiufang Yao; Hongxia Liu (Journal of Water Process Engineering, 2025)

Effects of simulated gastrointestinal digestion on protein degradation and bioactive peptides in Monascus cheese: a peptidomics and bioinformatics study - Xiangfei Jia; Qing Hong; Zhenmin Liu; Yuanrong Zheng; Xingmin Xu; Hanqing Wu; Yanping Hao (International Dairy Journal, 2025)

Unraveling the alkaloid diversity and pharmacological potential of Ocimum: Integrated UPLC-MS/MS, network pharmacology, and transcriptomic insights for functional food and drug discovery - Jingtian Yang; Jing Yuan; Mengling Yu; Yanping Mao; Mei Liu; Lingliang Guan; Lei Liu (Food Research International, 2025)

Naringenin attenuates Mandarin fish ranavirus (MRV)-induced hyperinflammation through the inhibition of MAPK and NF-κB signaling pathways - Ziye Zhang; Yanping Ma; Xinru Gao; Chaojiao Hu; Le Hao; Huijie Lu; Yugu Li; Zhenxing Liu (Fish & Shellfish Immunology, 2025)

Yeast-biomineralized MnOx modulates electron flux: Diverting carbon from methanogens to denitrifiers in carbon-limited wastewater - Yingying Liu; Xinshan Song; Xiaoxiao Hou; Yanping Xiao; Yuhui Wang; Xin Cao; Xiangzhou Meng (Environmental Research, 2025)

Formation of N-doped carbon nanosheets encapsulated hollow Co1/3Fe2/3P nanocrystals via the nanoscale Kirkendall effect as anode for superior alkali-ion batteries - Xijun Xu; Suping Chen; Fangkun Li; Panpan Zhang; Yanping Huo; Jun Liu (Chemical Engineering Journal, 2025)

Ru/S-modified hollow ZIF-67 for efficient sulfapyridine degradation via enhanced PMS-AOPs and inhibited of cobalt leaching - Zhuoqun Deng; Zhiyi Fan; Changchun Si; Jia Zhu; Ziyi Yang; Dexun Zou; Yanping Liu (Chemical Engineering Journal, 2025)

Suitable ridge width and straw length for alfalfa production under ridge-furrow rainwater harvesting compacted with chopped straw-soil crust in semiarid regions - Rizwan Azim; Qi Wang; Xuchun Li; Abdul Qadeer; Xiaole Zhao; Ibrahim Awuku; Wen Ma; Qinglin Liu; Yanping Liu; Bing Liu (Plant and Soil, 2025)

Assessing Spatiotemporal Characteristics, Health Impacts and Related Economic Losses of PM2.5, PM10 and O3 in Beijing-Tianjin-Hebei Region from 2015 to 2020 - Ran Gao; Qin Li; Yanping Zhang; Fei Che; Xiaorui Zhang; Yijie Wang; Yijun Zhang; Xite Zheng; Quanmei Li; Fengyi Huang; Chuning Luo; Wanqi Liu; et al. (Environment, Development and Sustainability, 2025)

Bioaugmentation with Caldibacillus thermoamylovorans improved methane production of thermophilic anaerobic digestion via enhancing hydrolysis and acidification processes - Mengyao Xiao; Na Wang; Lin Xu; Dongqing Cai; Yanping Zhu; Jiping Shi; Siying Zhang; Li Liu (Journal of Environmental Chemical Engineering, 2025)

Efficient activating peracetic acid by copper-aluminum composites to degrade sulfathiazole: The critical role of Cu(III) species - Yuxiao Mu; Yanping Ding; Linli Tan; Qiulin Shi; Lei Chen; Jiaqi Ding; Jingwen Wang; Yong Liu; Pengchao Xie (Journal of Environmental Chemical Engineering, 2025)

Effects of inorganic salt ions on long-term retrogradation characteristics of lotus seed starch under microwave treatment - Yingting Zhao; Zhiyang Lu; Yang Liu; Yanping Lei; Yuting Tian (Food Hydrocolloids, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

Synergistic bulk and back interface passivation enabled by in situ Ag-doping and Nb-engineering for efficient kesterite solar cells - Wenjie Zhu; Sisi Jia; Jingyi Meng; Chun Guo; Xinyu Zhang; Linxin Gao; Yixiang Xiao; Yanping Song; Jiayong Zhang; Huanhuan Sun; Jin Wang; Shihua Huang; et al. (Chemical Engineering Journal, 2025)

Ultrasound-triggered piezocatalytic MOF(Hf)-Pt nanozymes for efficient ROS scavenging in the treatment of osteoarthritis - Yi Yao; Zixin Gao; Zhongjie Pan; Yanping Zhong; Lili Qin; Kexin Zhao; Shuhan Liu; Shengqing Zhang; Haoyang Han; Feiying Yin; Ruizheng Liang; Jinmin Zhao; et al. (Chemical Engineering Journal, 2025)

Electron beam/persulfate-induced second-scale upcycling of wastewater polyvinyl alcohol with ultra-low chemical input - Tao Zhang; Yanping Zhu; Yongle Yu; Xiaoya Pan; Pan Zhao; Shihu Shu; Dongfang Wang; Jiping Shi; Li Liu; Weijian Zhang; Bin Huang; Xiaofeng Lu; et al. (Water Research, 2025)

Towards targeted heat resilience: A conceptual framework of urban heat-proof in Chengdu, China - Yutong Li; Sining Zhang; Xiaopeng Li; Shixian Luo; Qingling Liu; Yanping Zhong; Sheng Liu (Sustainable Cities and Society, 2025)

Dual regulation of microbial denitrification and methane mitigation with manganese-humic chelates - Yingying Liu; Xinshan Song; Xiaoxiao Hou; Yanping Xiao; Yuhui Wang; Xin Cao (Journal of Environmental Management, 2025)

Comparative analysis of sheep, goat, and cow milk based on non-targeted metabolomics - Jiaxin Liu; Zhongshi Zhu; Yanping Huang; Jianping Qin; Li Wang; Mengyao Wei; Xiaorui Liu; Liang Xu; Hao Yuan; Xiaopeng An; Lei Zhang; Yuxuan Song (International Dairy Journal, 2025)

Contribution of solar photovoltaic to the decarbonization of wastewater treatment plants in China - Ranbin Liu; Yanping Qiao; Huanlun Zhang; Maokun Lv; Xiaodi Hao (Desalination, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

Functional integrated in gel polymer electrolytes: A handy approach for achieving superior wide temperature range operation sodium metal batteries - Yubin Liao; Fangkun Li; Yadong Zhou; Xijun Xu; Hangyu Zhang; Weizhen Fan; Yanxue Wu; Jingwei Zhao; Jun Liu; Yanping Huo (Chemical Engineering Journal, 2025)

Development of hydroxyapatite-based Carboxymethylcellulose-Al(III) aerogel beads for efficient and selective defluorination from brick tea infusions - Wenyue Yu; Huan Guo; Ya Liu; Yangyu Zhou; Yue Xiao; Jinrong Bai; Yanping Wu; Kai Zhong; Yina Huang; Hong Gao (Carbohydrate Polymers, 2025)

Corrosion characteristics of low-carbon cast steel ZG230-450 in chloride-sulfate atmospheric environment - Xuan Zheng; Yanping Zhao; Hongxin Yang; Baorong Liu; Chi Zhang (Environmental Science and Pollution Research, 2025)

Mn-doped copper slag with oxygen vacancies boosts peroxymonosulfate activation for ofloxacin rapid removal - Linjin Li; Yaoze Wang; Guangfei Qu; Nanqi Ren; Yanping Liu; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Yingying Cai; Xiaofei Li; Rui Xu (Journal of Water Process Engineering, 2025)

Hydroxyl-tunable type I photosensitizer based on curcumin for photodynamic therapy against hypoxic tumor cells - Yanping Wang; Tong Mu; Xuewei Li; Xiuli Zheng; Jie Sha; Zhe Yu; Yuanyuan Qin; Haohui Ren; Ying Wang; Weimin Liu; Pengfei Wang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Selenium-doped NiCo2O4 drives nanozyme innovation: new ideas in water disinfection - Yanping Feng; Zizhuo Liu; Kexin Zhang; Fanyan Deng; Congqin Ning (Journal of Cleaner Production, 2025)

Titanium dioxide nanoparticles disturb glucose homeostasis in association with impaired enteroendocrine cell differentiation - Kai Zou; Linna Du; Jing Qin; Jiacheng Zhou; Yanping Xiao; Xixi Song; Hongxia Liu; Xiu Wang (Food and Chemical Toxicology, 2025)

Energy saving and carbon reduction benefits of ventilated photovoltaic walls combined with non-balanced thermal insulation in Lhasa residential buildings - Xinrong Zhu; Daijun Huang; Yanyan Niu; Yan Liu; Yanping Yuan; Liu Yang; Jiaping Liu (Energy and Buildings, 2025)

DNA damage repair (DDR) related prognostic risk model in multiple myeloma based on single-cell and bulk sequencing - Hongxiu Liu; Zhihua Li; Yihua Wang; Can Li; Kaiqing Yan; Yanping Ma (DNA Repair, 2025)

Cobalt doping modulation of Cs4MnBi2Cl12 double perovskite induces spin polarization for boosting photocatalytic reduction of CO2 - Yan Huang; Yujia Liu; Yi Liu; Xinqiu Tan; Yikai Wang; Qian Xiao; Xiaoyu Tong; Jinghui Pan; Zebin Yu; Zuofang Yao; Yanping Hou (Chemical Engineering Journal, 2025)

Enhancing manganese redox-driven nitrogen removal by integrating manganese ore with microelectrolysis into constructed wetlands - Xiaoxiao Hou; Wei Huang; Xinshan Song; Yingying Liu; Yanping Xiao; Xiaoxiang Zhao; Dong An (Bioresource Technology, 2025)

Melatonin Ameliorates Senescence of Mouse Auditory Cell Line HEI-OC1 Cells by Suppressing NLRP3 Inflammasome-Mediated Pyroptosis - Yongqing Ding; Yachao Liu; Dong Li; Ruili Hu; Zedong Tian; Lihang Yang; Yanping Li; Yantao Lin; Yan Qu (Molecular Neurobiology, 2025)

OCCMNet: Occlusion-Aware Class Characteristic Mining Network for multi-class artifacts detection in endoscopy - Chenchu Xu; Yu Chen; Jie Liu; Boyan Wang; Yanping Zhang; Jie Chen; Shu Zhao (Medical & Biological Engineering & Computing, 2025)

Apoptosis in spotted sea bass brain and astroglia-like cell line implies a possible pathogenesis of Lateolabrax maculatus iridovirus infection - Jingjing Xu; Yanping Ma; Le Hao; Zhenxing Liu (Fish Physiology and Biochemistry, 2025)

The poleward expansion of the Hadley Cell has weakened the winter circulation in a midlatitude semi-enclosed shelf sea over the past six decades - Fangguo Zhai; Hao Li; Yanping Ma; Yucheng Wang; Yujie Dong; Zizhou Liu; Yanzhen Gu; Peiliang Li (Climate Dynamics, 2025)

Dynamics of wall bubbles in flash evaporation systems: Heterogeneous expansion and microlayer development - Qifan Wang; Junren Hou; Shanfang Huang; Fangbei Chen; Minyun Liu; Ruohan Zheng; Yanping Huang; Lie Quan; Houjun Gong; Yu Tang (Annals of Nuclear Energy, 2025)

Persistent Wnt signaling affects IVF embryo implantation and offspring metabolism - Yanping Jia; Yingdong Liu; Yanhe Li; Xiaohong Guan; Junting Xu; Zihui Yan; Kuisheng Liu; Yalin Zhang; Dandan Bai; Jiani Xiang; Yan Zhang; Shangyu Hou; et al. (Science Bulletin, 2025)

Impact of microplastics on plant biogenic volatile organic compounds emission: A preliminary study - Shuqin Liu; Shengmei Feng; Yanping Zhang; Yang Zheng; Ruifen Jiang; Gangfeng Ouyang (Journal of Hazardous Materials, 2025)

Hydrothermal reduction and phase transformation of Fe(III) minerals induced by rice straw to improve the heterogeneous Fenton degradation of metolachlor - Jingyi Liu; Yu Zhao; Liulong Cheng; Zhuoye Lu; Haojie Liang; Runliang Zhu; Yue Wang; Fangxin Deng; Zhuobiao Ni; Yaying Li; Guangwei Yu; Jing Zhang; et al. (Journal of Hazardous Materials, 2025)

Polyphenylene molecular engineering enables highly efficient multi-resonance thermally activated delayed fluorescence emitters with quenching resistance - Longjiang Xing; Xiaofeng Wang; Xiaolong Liu; Wen-Cheng Chen; Shihao Liu; Siwei Chen; Mengke Li; Ji-Hua Tan; Jia-Ming Jin; Ruicheng Wang; Shangru Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Rewiring the methanol assimilation pathway in the methylotrophic yeast Pichia pastoris for high-level production of erythritol - Shuxian Wang; Jiayu Fang; Meiyu Wang; Sijie Yu; Yan Xia; Guoxia Liu; Yanping Zhang; Yin Li; Taicheng Zhu (Bioresource Technology, 2025)

The independent and joint effects of meteorological factors on influenza: A nationwide time series study in China - Mengen Guo; Yunfei Zhang; Jianxiong Hu; Aga Zheng; Guanhao He; Xiaokun Yang; Hongting Zhao; Tao Liu; Fengrui Jing; Ziqiang Lin; Yanping Zhang; Maigen Zhou; et al. (Urban Climate, 2025)

Synthesizing ZIF-8 functionalized biochar by in situ reuse of residual Zn from chemical activation for enhanced tetracycline hydrochloride adsorption removal - Jianying Liu; Qian Zeng; Yao Chen; Zhongde Dai; Wenju Jiang; Lu Yao; Junfeng Zheng; Dengrong Sun; Yanping Wu; Lin Yang (Journal of Environmental Chemical Engineering, 2025)

Influence of tin doping on the activity and mechanism of CeO2 catalyst for selective catalytic reduction of NO with NH3 - Jingsong Zhou; Yanping Du; Yuqing Qiao; Fei Zhou; Zhou Liu; Zhibo Xiong; Mengqi Liu; Wei Lu (Journal of Environmental Chemical Engineering, 2025)

Redox-active ligands for oxygen evolution reactions activity: Modulation of metal valence states in synthesis and accelerated reconstruction by rapid hydrolysis in alkaline electrolytes - Pengxin Sun; Jing Liu; Li Wang; Cheng Wu; Ronghua Jiang; Jun Huang; Yanping Hou; Mingjie Li; Boge Zhang; Zebin Yu (Journal of Environmental Chemical Engineering, 2025)

Effects of Fe3O4 on production of even-carbon volatile fatty acids by anaerobic fermentation of kitchen waste under ultrasonic-alkali pretreatment: Performance, metabolic functions, and metabolic pathways - Ziang Wang; Rufei Liu; Yue Cui; Zhihan Zhang; Huiyan Jing; Zhiling Chen; Shen Tian; Ziyi Yang; Yanping Liu (Journal of Environmental Chemical Engineering, 2025)

W2O6/CoFe2O4: An efficient catalyst to activate peroxymonosulfate for the elimination of antibiotic-resistant bacteria and genes in aquaculture effluent - Yanqiong Zhang; Muting Yan; Gaoling Wei; Fengru Lu; Feng Li; Peng Liu; Yanping Zhu; Han Gong (Journal of Environmental Chemical Engineering, 2025)

Research on PWV fusion based on ERA5 PWV and FY-4A PWV in Chinese mainland - Wei Du; Yong Wang; Xiao Liu; Jing Huang; Yanping Liu; Xiangshun Meng (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Alkaline-thermal synergistic activation of persulfate for sawdust hour-level humification to prepare fulvic-like-acid fertilizer - Dongfang Wang; Xinyan Chen; Jing Zhang; Jia Xu; Xianghai Kong; Jinghong Ye; Rongjun Zhang; Huiqun Fan; Li Liu; Xiuping Zhan; Yan Qin; He Xu; et al. (Bioresource Technology, 2025)

Effects of trigonelline, diosgenin, and Cistanche deserticola polysaccharide on the culture of female germline stem cells in vitro - Xiaoli Yu; Yikai Qiu; Jinhua Li; Yanping Zhang; Qian Wang; Zehua Jin; Xinrui Liu; Xiuying Pei (Natural Product Research, 2025)

Advancements in lipid-based delivery systems for functional foods: a comprehensive review of literature and patent trends - Xidong Liu; Zengliu Song; Wenni Tian; Abdullah; Qingrong Huang; Meimiao Chen; Yanping Huang; Hang Xiao; Jie Xiao (Critical Reviews in Food Science and Nutrition, 2025)

Hybrid Path Planning Method for USV Based on Improved A-Star and DWA - Yan Liu; Zeqiang Sun; Junhe Wan; Hui Li; Delong Yang; Yanping Li; Wei Fu; Zhen Yu; Jichang Sun (Journal of Marine Science and Engineering, 2025)
This paper presents a hybrid path planning method that integrates an enhanced A-Star algorithm with the Dynamic Window Approach (DWA). The proposed approach addresses the limitations of conventional A-Star algorithms in global path planning, particularly their inability to adaptively avoid obstacles in real-time. To improve navigation safety, the A-Star search strategy is enhanced by avoiding paths that intersect with obstacle vertices or pass through narrow channels. Additionally, a node optimization technique is introduced to remove redundant nodes by checking for collinearity in consecutive nodes. This optimization reduces the path length and ensures that the path maintains a safe distance from obstacles using parallel lines. An advanced Bézier curve smoothing method is also proposed, which adaptively selects control points to improve path smoothness and driving stability. By incorporating these improvements, the enhanced A-Star algorithm is combined with DWA to facilitate dynamic obstacle avoidance while generating global paths. The method accounts for the kinematic characteristics of the USV, as well as physical constraints such as linear and angular velocities, enabling effective handling of obstacles in dynamic environments and ensuring safe navigation. Simulation results demonstrate that the proposed algorithm generates secure global paths, significantly optimizing node count, path length, and smoothness, while effectively avoiding dynamic obstacles, thus ensuring safe navigation of the USV.

The application of amendments improves properties of salt-affected soils across China - Guangzhi Huang; Baishun Liu; Xiaotong Jiang; Yanping Liang; Jinghui Cai; Lihua Huang (Soil and Tillage Research, 2025)

Montmorillonite-enhanced Carboxymethylcellulose/Polyethyleneimine aerogel: A highly efficient and reusable adsorbent for caffeine removal from tea infusions - Wenyue Yu; Yangyu Zhou; Ya Liu; Huan Guo; Lihui Huang; Lu Feng; Jinrong Bai; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Hong Gao (Food Chemistry, 2025)

Critical review on food packaging strategy against spoilage - Lei Liu; Youwei Jiang; Kun Wan; Yanping Wei; Du Tuo; Chuanqin Zhou; Quanguo He; Yimin Tan (Food and Humanity, 2025)

An advanced numerical model for dynamic daylight and energy consumption analysis of thermal-responsive complex fenestration system with adaptive solar absorption - Yang Ming; Mingke Hu; Xiao Liu; Yanping Yuan; Yupeng Wu (Energy and Buildings, 2025)

Preparation of a polysulfone loose nanofiltration membrane with gradient structure via hybrid-induced phase separation for the efficient separation of dyes/salts - Yuanhui Tang; Huifang Yu; Yuwenyao Zhang; Juan Liu; Jihao Zhu; Yakai Lin; Hedi Chen; Yanping Hu; Jianqing Zhang; Song Hu; Hai Xie; Lixin Yu; et al. (Desalination, 2025)

Selective adsorption of Rb+ and Cs+ by a superparamagnetic Fe₃O₄@FeMn-MOF from brine - Yanping Wang; Qiongyuan Zhang; Dezhen Fang; Kexin Li; Zhongmei Song; Wenjie Han; Junwei Li; Xiushen Ye; Haining Liu; Huifang Zhang; Xi Zhang; Zhijian Wu (Desalination, 2025)

Study on liquid phase separation phenomenon by constructing multi-physics field model - Kerong Guo; Houjun Gong; Rongpei Shi; Yuanfeng Zan; Yihui Guo; Xingjun Liu; Yanping Huang (Annals of Nuclear Energy, 2025)

Chemical fractionation and isotopic analysis of lead in sediments from the Taipu River, integrated demonstration zone in the Yangtze River Delta, China - Yaojen Tu; Pengcheng Luo; Meichuan Chien; Yanping Duan; Jiayi Kou; Shenghui Liu; Yalong Li (Journal of Environmental Chemical Engineering, 2025)

Proteomic insights from extracellular vesicles into the molecular mechanisms of health effects induced by Per- and polyfluoroalkyl substances - Yanping Li; Yadan Luo; Yang Liu; Na Li; Kai Huang; Lingxiangyu Li; Zhigang Li; Chao Han; Nali Zhu; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2025)

Comprehensive lipid profiling and metabolic pathway analysis of Ocimum: Unveiling key variations and regulatory mechanisms for breeding and metabolic exploration - Jingtian Yang; Chengting Zhang; Mengling Yu; Jing Yuan; Yanping Mao; Mei Liu; Lei Liu; Lingliang Guan (Food Bioscience, 2025)

Study of the interaction between polysaccharides and liposomes based on low-field nuclear magnetic resonance - Tingting Zhang; Heng Yu; Chenping Li; Yanping Wang; Chenxi Zheng; Yingli Hu; Jianzhong Han; Jianhua Liu; Weilin Liu (Food Bioscience, 2025)

Identification of candidate genes associated with resistance to aflatoxin production in peanut through genetic mapping and transcriptome analysis - Dongxin Huai; Li Huang; Xiaomeng Xue; Bolun Yu; Yingbin Ding; Gaorui Jin; Hao Liu; Manish K. Pandey; Hari Kishan Sudini; Huaiyong Luo; Xiaojing Zhou; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Mixed vineyard prunings and sheep manure compost: Creating changes in vineyard soil dominant microbiota to impact fruit quality - Qian Tu; Yuanyuan Li; Weikang Ding; Shubo Zhou; Yanping Huang; Shiqiu Liu; Xuwu Min; Jiarui Zhang; Junjun Li; Chunlong Yuan (Applied Soil Ecology, 2025)

Research on the fusion of PWV over the Beijing-Tianjin-Hebei region based on ERA5 PWV and FY-4A PWV - Wei Du; Yong Wang; Xiangshun Meng; Yanping Liu; Xiao Liu (Advances in Space Research, 2025)

Lycorine provides antiviral activities against mandarin fish ranavirus via suppressing apoptosis and activating type I interferon pathway - Mengyan Jia; Yanping Ma; Le Hao; Ziqian Tao; Jingya Wang; Sentai Liao; Hui Guo; Zhenxing Liu (Aquaculture, 2025)

Chinese chestnut did not induce negative plant soil feedback during centuries of growth - Xu Cheng; Zhichun Yan; Qian Li; Lucas Schmitz; Jundi Yan; Yueyang Ge; Yanping Lan; Yaceng Zhao; Yiyang Wang; Guangdong Li; Yang Liu; Martinus Schneijderberg; et al. (Science of The Total Environment, 2025)

Prenatal high-sucrose diet affects pulmonary artery contractile functions via MT receptors - Xueqin Feng; Hongwei Fu; Xiao Sun; Hua Shu; Yongning Zhu; Yanyan Bai; Qinggui Ren; Xinying Liu; Meng Liu; Fanyong Zhang; Yanping Wang (Reproductive Toxicology, 2025)

Self-healing physiological monitoring epidermal sensors of dual conductivity pathway with self-adaptive transformation - Liao Ziming; Zhu Ximing; Zhang Shuquan; Liu Tingting; Song Jiamei; Wang Yuhong; Guo Yanping; Li Xiaohong; Ji Xiaoyuan; Yao Bin (Chemical Engineering Journal, 2025)

Monosome Stalls the Translation Process Mediated by IGF2BP in Arcuate Nucleus for Puberty Onset Delay - Yifen Shen; Le Zhang; Tao Yang; Xiaosong Li; Chao Liu; Hongmei Li; Yanping Hu; Hao Shen; Hua Li; Yuriy L. Orlov; Shasha Zhou; Yihang Shen (Molecular Neurobiology, 2025)

Three-dimensional changes in temperature and circulation caused by northwestward-moving typhoons in a temperate semi-enclosed shelf sea in summer - Yanping Ma; Fangguo Zhai; Xingchuan Liu; Cong Liu; Zizhou Liu; Yanzhen Gu; Peiliang Li (Frontiers in Marine Science, 2025)
Due to the complex coastline and topography, changes of temperature and circulation in global shelf seas caused by typhoons have significantly region-specific three-dimensional structures. As one temperate semi-enclosed shelf sea, the Yellow Sea is highly susceptible to typhoons in summer. In August 2012 Typhoon Damrey moving northwestward over the Yellow Sea was observed to cause significant bottom temperature warming in the southern coastal waters of the Shandong Peninsula, but its impacts on the three-dimensional changes of temperature and circulation in the whole Yellow Sea and the underlying dynamics are still unclear. Using observations and high-resolution numerical simulations, we showed that during Damrey’s passage the South Yellow Sea exhibited spatially coherent surface cooling, particularly forming a distinct surface cooling band on the right side of the typhoon track. With the mixed layer deepening, the subsurface layer deepened and experienced temperature warming, especially on the right side of the typhoon track. The surface cooling and subsurface warming were primarily caused by strong wind-enhanced vertical mixing. In the deep layer, temperature exhibited pronounced warming in the southern coastal waters of the Shandong Peninsula but cooling in a southeast-northwest band along the bottom slope just off the Subei Shoal. Bottom temperature warming in the southern coastal waters of the Shandong Peninsula was caused by coastal downwelling resulting from upper layer coastward Ekman transport. Conversely, vertically consistent temperature cooling just off the Subei Shoal was caused by coastward and upward advection of cold water across the temperature fronts and thermocline due to surface layer Ekman divergence. The intensity and spatial distributions of temperature cooling just off the Subei Shoal were related to the distance between the typhoon track and Subei Shoal. Closer proximity of the typhoon track to the Subei Shoal would lead to more pronounced bottom cooling. This study enriches our understanding of three-dimensional hydrodynamic changes induced by typhoons with different tracks in the Yellow Sea.

Neurotoxicity study of cenobamate-induced zebrafish early developmental stages - Jiahao Liu; Liya Fang; Chao Gong; Jiawei Li; Yuanyuan Liu; Pei Zeng; Yanping Fan; Yao Liu; Jin Guo; Luchuan Wang; Yue Li (Toxicology and Applied Pharmacology, 2025)

Microtopography-induced hydrological heterogeneity promotes the co-assembly of vascular plant and biocrust communities, providing synergistic protective functions for the Great Wall - Yanping Liu; Wanfu Wang; Jing Ren; Yanhong Gao; Fasi Wu; Yafei Shi; Hongtao Zhan; Chengxu Chi; Rongliang Jia (Science of The Total Environment, 2025)

Boosting electrocatalytic performance of BaPrO3-δ −based cathode catalysts by Co and Ni co-doping for protonic ceramic fuel cells - Bo Liu; Yanping Zheng; Xinwei Yang; Yaping Liu; Dong Yan; Jian Li; Lichao Jia (Chemical Engineering Journal, 2025)

Development of system analysis code and its application in transient simulation of supercritical CO2 Brayton cycle direct cooled reactors - Haijie Wu; Minyun Liu; Shenghui Liu; Jiatao Meng; Shuangqing Chen; Ruohan Zheng; Yanping Huang; Houjun Gong; Xiaoliang Zhu; TianYang Xing; Mudi Jiang (Annals of Nuclear Energy, 2025)

Temporal dynamics of summer phytoplankton communities and their response to environmental changes in the northern Yellow Sea (2011-2020) - Yibo Wang; Zhiliang Liu; Yanping Qi; Yang Chen; Haibo Zhang; Xihan Liu; Du Su (Frontiers in Marine Science, 2025)
Research on phytoplankton distribution and dynamics is crucial for understanding marine ecosystem functions and evaluating their status. The northern Yellow Sea (NYS), a marginal sea of the Pacific Ocean, has experienced significant anthropogenic impacts since the late 20 th century, resulting in an increased nitrogen-to-phosphorus (N/P) ratio and heightened phosphorus limitation. These changes are considered critical factors affecting the phytoplankton community structure in the NYS over recent decades. This study analyzed the temporal dynamics of environmental factors and phytoplankton community structure in the NYS during the summers from 2011 to 2020, aiming to elucidate recent changes in phytoplankton community structure and their driving forces. The results indicated a significant decrease in dissolved inorganic nitrogen (DIN) concentration after 2011, resulting in a decreased N/P ratio, while phosphorus limitation persisted. Temperature, temperature gradient (reflecting stratification intensity) and salinity exhibited upward trends, whereas pH, nitrogen-to-silicon (N/Si) ratio, and chlorophyll- a concentration showed downward trends. The abundances of total phytoplankton, Bacillariophyta, and Dinoflagellata, as well as the Dia/Dino index, fluctuated annually and correlated with temperature, temperature gradient, and nutrient structure. Diversity indices remained stable throughout the study period. The Yellow Sea Cold Water Mass prominently influenced summer phytoplankton community structure, exhibiting lower phytoplankton abundance, Dia/Dino index, and species richness in the cold water mass region, where adaptable species such as Tripos muelleri and Paralia sulcata predominated. Our results emphasized the impact of environmental changes associated with climate change, including rising temperatures, increased salinity, and enhanced stratification, on the phytoplankton community structure in recent years, particularly concerning the dominant species composition and the Dia/Dino index. Therefore, ongoing attention to the effects of climate change on coastal environments and phytoplankton communities is essential.

Facile fabrication of porous fluorinated polyurethane membranes for organic solvent adsorption based on thiol-ene click reaction within high internal phase emulsions - Aili Wang; Yuyang Liu; Yanping Yu; Minxin Song; Jinyue Li; Yutong Wang; Caiyang Zhang; Nan Lou; Fang Qi; Xueyi Han (Process Safety and Environmental Protection, 2025)

An enhancer–promoter-transcription factor module orchestrates plant immune homeostasis by constraining camalexin biosynthesis - Ying Zhang; Meng Tang; Yi Zhang; Qinglin Cheng; Lijiang Liu; Wei Chen; Jiatao Xie; Jiasen Cheng; Yanping Fu; Bo Li; Daohong Jiang; Xiao Yu (Molecular Plant, 2025)

Salicylic acid cooperates with different small molecules to control biotic and abiotic stress responses - Kexing Xin; Yining Wu; Aziz Ul Ikram; Yanping Jing; Shan Liu; Yawen Zhang; Jian Chen (Journal of Plant Physiology, 2025)

Multiple-cation doped LaCl3-based chloride solid-state electrolyte compatible with lithium metal - Xuxia Hao; Kai Chen; Min Jiang; Yanping Tang; Yuexin Liu; Kefeng Cai (Chemical Engineering Journal, 2025)

Ultrafine Na3V2(PO4)3@C with boosted interfacial charge transfer kinetics for low-temperature (−40 °C) Na-ion battery - Yanjing Liu; Shitan Xu; Huacheng Zhu; Yang Yang; Yang Yang; Yanping Zhou; Xianhong Rui (Chemical Engineering Journal, 2025)

Effects of cloprostenol and oxytocin on ultrasonographic changes of uterine horns in postpartum primiparous Hu sheep - Yixuan Li; Zongling Liu; Wenqian Zhang; Chunhao Zhu; Xi Chen; Yukun Zhao; Lei Liu; Ting Ting Zhu; Mingyang Geng; Yanping Wang; Weibin Zeng (Animal Reproduction Science, 2025)

Mandarin Fish Ranavirus ( MRV ) Infection Induced Inflammation and Histologic Lesions in the Gut of Mandarin Fish - Xinru Gao; Ziye Zhang; Yanping Ma; Le Hao; Wen Huang; Zhenxing Liu; Yugu Li (Journal of Fish Diseases, 2025)
Mandarin fish ranavirus (MRV) is widely spread in China and causes huge economic losses to the mandarin fish ( Siniperca chuatsi ) aquaculture. However, the pathogenesis of MRV is still unclear. In the present study, mandarin fish were artificially infected with MRV, and then different gut compartments from diseased fish were subjected to histologic analysis by H&E staining, quantification of proinflammatory genes and MRV copies by qPCR. MRV‐MCP protein expression was assessed using indirect fluorescence assay (IFA) and immunohistochemistry. Proliferation of IgM + B cells was evaluated by indirect fluorescence assay (IFA). Then, we found that MRV infection caused serious histologic lesions along with inflammatory cell infiltration, especially in the foregut. A significant accumulation of IgM + B cells was detected in the foregut (~6.5‐fold) and hindgut (~3.3‐fold), respectively. The expression of inflammation‐related genes such as IL‐1β, IL‐6, IL‐8, TNF‐α, CSF1r and NCF1 was significantly upregulated in the foregut, varying from ~2.8‐fold to ~11.9‐fold. In addition, MRV exhibited foregut tropism, according to the investigation of viral loads and MCP protein expression. Overall, our findings indicated that MRV‐induced hyperinflammation in the gut eventually led to enteritis. This study provided new insights into uncovering the pathogenesis of MRV infection.

Monoclonal antibody development and antigenic epitope identification of infectious bursal disease virus VP5 - Jinze Han; Xinxin Niu; Chengfei Ge; Ziwen Wu; Guodong Wang; Mengmeng Huang; Yulong Zhang; Runhang Liu; Mengmeng Xu; Hangbo Yu; Jingzhe Han; Suyan Wang; et al. (The Veterinary Journal, 2024)

Climate change drives fish communities: Changing multiple facets of fish biodiversity in the Northwest Pacific Ocean - Shuhao Liu; Yang Liu; Qinwang Xing; Yuru Li; Hao Tian; Yanping Luo; Shin-ichi Ito; Yongjun Tian (Science of The Total Environment, 2024)

Research on parametric roll of the polar environmental transport ship based on time-domain Rankine panel method - Wei Zhang; Yadong Liu; Yanping He; Yan Zhou; Dong Wang; Yuying Tang; Jianmei Chen (Ocean Engineering, 2024)

Remediation of hexavalent chromium contaminated soils by stimulating indigenous microorganisms: Optimization, community succession and applicability - Xusheng Zheng; Jingjing Tong; Shufang Zhou; Yanping Liu; Guangqing Liu; Dexun Zou (Journal of Environmental Management, 2024)

An evaluation method for synergistic effect of air pollutants and CO2 emission reduction in the Chinese petroleum refining technology - Dandan Liu; Xueying Li; Dong Wang; Hao Wu; Yanping Li; Yanjun Li; Qi Qiao; Zhou Yin (Journal of Environmental Management, 2024)

Novel advanced oxidation technology of Fe2+-activated peracetic acid for high efficient disintegration of waste activated sludge - Wenqi Liu; Yanping Zhang; Jing Zhang; Ning Lv; Yibing Li (Journal of Environmental Chemical Engineering, 2024)

Ferrihydrite optimizing Feammox inoculum to enhance ammonia removal from concentrate wastewater through continuous upflow anaerobic sludge blanket (UASB) - Linji Xu; Lin Li; Jianxi Liu; Xingzu Wang; Yanping Zhao; Jujiao Zhao; Li Gu; Qiang He; Xinzhu Wang; Jinhua Zhang (Journal of Environmental Chemical Engineering, 2024)

Promotional effect of microwave radiation treatment on the desorption of CO2 from mono-ethanolamine (MEA) solution over FeOOH catalyst - Haoran Zhang; Junge Lv; Zhibo Xiong; Huancong Shi; Jing Jin; Mengqi Liu; Yanping Du; Wei Lu (Journal of Environmental Chemical Engineering, 2024)

Characterization of the key odorants in goji wines in three levels of sweetness by applications of sensomics approach - Yan Zheng; Claudia Oellig; Youfeng Zhang; Yuan Liu; Yanping Chen; Yanyan Zhang (Food Chemistry, 2024)

Unveiling the adsorption behavior and mass transfer mechanism of Rb+ and Cs+ adsorption on FeMn-MOF - Yanping Wang; Xiushen Ye; Qiongyuan Zhang; Wenjie Han; Xing Liu; Huifang Zhang; Haining Liu; Zhijian Wu; Guosheng Shi (Chemical Engineering Journal, 2024)

Construction of structure-matching In-Ni catalysts for the selective hydrogenation of α-methylacrolein - Lin Ai; Yanping Chen; Fang Lu; Jiaxu Liu; Xiao-Feng Wu; Shengjun Huang (Chemical Engineering Journal, 2024)

Construction of a redox-coupled pathway co-metabolizing glucose and acetate for high-yield production of butyl butyrate in Escherichia coli - Tianrui Zhang; Guoxia Liu; Yin Li; Yanping Zhang (Bioresource Technology, 2024)

Field experiment on transient thermal comfort in a Chinese railway station – High temperature exposures - Xiaowen Su; Wei Liu; Richard de Dear; Liangliang Sun; Yanping Yuan (Building and Environment, 2024)

Biological invasion is eroding the unique assembly of island herpetofauna worldwide - Weishan Tu; Yuanbao Du; Yoel E. Stuart; Yanxia Li; Yanping Wang; Qingfa Wu; Baocheng Guo; Xuan Liu (Biological Conservation, 2024)

Enhanced 3D dose prediction for hypofractionated SRS (gamma knife radiosurgery) in brain tumor using cascaded-deep-supervised convolutional neural network - Nan Li; Jinyuan Wang; Yanping Wang; Chunfeng Fang; Yaoying Liu; Chunsu Zhang; Dongxue Zhou; Lin Cao; Gaolong Zhang; Shouping Xu (Physical and Engineering Sciences in Medicine, 2024)

Numerical investigation on effects of fuel rod with the position of bow deformation on the flow and heat transfer of PWR - Chengde Li; Mei Huang; Delong Sun; Xiaoping Ouyang; Yanping Huang; Yang Liu (Annals of Nuclear Energy, 2024)

Recombinant Marek’s disease virus type 1 provides full protection against H9N2 influenza A virus in chickens - Yuntong Chen; Qingqing Yu; Wenrui Fan; Xianying Zeng; Zibo Zhang; Guobin Tian; Changjun Liu; Hongmei Bao; Longbo Wu; Yanping Zhang; Yongzhen Liu; Suyan Wang; et al. (Veterinary Microbiology, 2024)

Microplastics distribution, ecological risk and outflows of rivers in the Bohai Rim region of China - A flux model considering small and medium-sized rivers - Xin Hou; Jiayao Li; Hongyu Li; Shuyun Du; Sitong Liu; Shipu Jiao; Fuxin Niu; Jianbo Tu; Yanping Zong; Xiaotong Wang; Xianhua Liu (Science of The Total Environment, 2024)

Vascular plants and biocrusts ameliorate soil properties serving to increase the stability of the Great Wall of China - Yanping Liu; Jing Ren; Wanfu Wang; Yafei Shi; Yanhong Gao; Hongtao Zhan; Yayong Luo; Rongliang Jia (Science of The Total Environment, 2024)

Numerical simulation and deep-sea experiment validation for the cathodic protection design of aluminum alloy framework - Tigang Duan; Yu Zhang; Li Ma; Shaohua Xing; Yanping Liu; Wenshan Peng; Haibing Zhang; Jian Hou (Ocean Engineering, 2024)

Impact of geochemistry and microbes on the methylmercury production in mangrove sediments - Jingli Liu; Yanping Li; Aijia Zhang; Huan Zhong; Hao Jiang; Martin Tsz-Ki Tsui; Meng Li; Ke Pan (Journal of Hazardous Materials, 2024)

Can combined wind and solar power meet the increased electricity load on heatwave days in China after the carbon emission peak? A case study in southern Hebei - Jie Bai; Mingxin Zhao; Xiaohui Qin; Yanping Xu; Yang Liu (Journal of Cleaner Production, 2024)

Driving mechanism of land use and landscape pattern to phytoplankton and zooplankton community and their trophic interactions in river ecosystems - Litao Hao; Yixin Zhang; Yanping Shen; Yibo Liu; Hongjie Gao; Ping Guo (Journal of Environmental Management, 2024)

Uncovering the Shuixian tea grades hierarchy in Chinese national standard: From sensory evaluation to microstructure and volatile compounds analysis - Yanping Lin; Yibiao Huang; Xia Liu; Yani Pan; Xinyu Feng; Haowei Guo; Xiaolan Li; Yike Tao; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Dynamic of phytoplankton community during varying intensities of the northeast monsoon in the Taiwan Strait - Yanping Zhong; Peixuan Wang; Jinxin Chen; Xin Liu; Edward A. Laws; Bangqin Huang (Acta Oceanologica Sinica, 2024)

ChCaspase-1 cleaves ChGasdermin-E, inducing pyroptosis, and participates in the bacterial defence of the oyster Crassostrea hongkongensis - Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Ruwen Yang; Shu Xiao; Fan Mao; Yanping Qin; Haitao Ma; Yuehuan Zhang; Yang Zhang; ZiniuYu; et al. (Aquaculture, 2024)

Facile in-situ fabrication of graphene oxide/poly(ionic liquid) composites and their adsorption performance for methyl orange - Xiaoying Wang; Yuyang Liu; Xiuzhi Liu; Caiyang Zhang; Minxin Song; Yanping Yu; Xueyi Han; Jinyue Li; Aili Wang (Process Safety and Environmental Protection, 2024)

New role of radical-induced polymerization: Base/self-heating synergistically activate persulfate to boost food waste humification - Dongqing Cai; Xiaoya Pan; Chengjin Wang; Shihu Shu; Pengjin Zhu; Chunhuo Zhou; Dongfang Wang; He Xu; Yanbiao Liu; Wenhai Chu; Xiang Li; Yanping Zhu (Journal of Cleaner Production, 2024)

Upcycling of nutrients from kitchen waste: Integration of anaerobic digestion system and microbial protein production system - Qile Zhu; Kangjian Gao; Qi Sun; Chuan Ma; Yuxing Luo; Zijin Niu; Yanping Liu; Ziyi Yang (Journal of Environmental Management, 2024)

Proton transfer induced persistent triplet charge transfer phosphorescence in molecule-doped polymer systems - Shulin Liu; Chensheng Li; Liyun Liao; Yanping Huo; Zhong-Min Su; Fu-Shun Liang; Yingxiao Mu (Chemical Engineering Journal, 2024)

Quinary metal oxide NiCoMnCeCaOx nanorod as a multifunctional catalyst towards hydrogen production from ethanol steam reforming: Synergistic effect of polymetallic component - Mingzheng Liao; Chunrun Qin; Liujie Xu; Sihan Guo; Chao Wang; Yi Li; Wei Liu; Qingbin Song; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Understandings in surface metal exsolution of NiFeZn ternary alloy/spinel in ethanol steam reforming: The key to hydrogen production - Mingzheng Liao; Wei Liu; Congkang Li; Sihan Guo; Yanyu Chen; Chao Wang; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Heterostructure-anchored 3D CNT-bridged graphene architecture via layer-by-layer structural engineering for thick electrodes of supercapacitors - Yanping Song; Nian Li; Jun Kang; Zhao Li; Na Hong; Shuai Han; Liqing Chen; Shudong Zhang; Cui Liu; Congfa Song; Jiakuan Zhang; Zhenyang Wang (Chemical Engineering Journal, 2024)

Numerical simulation on staggered grids of three-dimensional brinkman-forchheimer flow and heat transfer in porous media - Wei Liu; Yingxue Song; Yanping Chen; Gexian Fan; Pengshan Wang; Kai Li (Computational Geosciences, 2024)

Response of phytoplankton communities to environmental changes in the Bohai Sea in late summer (2011–2020) - Yibo Wang; Zhiliang Liu; Yanping Qi; Xiao Chen; Yang Chen; Du Su; Xiaobo Yuan; James Klippel-Cooper (Acta Oceanologica Sinica, 2024)

The practice and innovation of compatible marine utilization models in China - Yanping Li; Yan Yang; Yuting Hou; Xiao Liu; Dahai Liu (Frontiers in Marine Science, 2024)
Marine Spatial Planning (MSP) is essential for optimizing marine resources allocation and resolving conflicts in sea use, but it is challenged by the complex and multi-functional nature of maritime resources. This study utilizes participatory methods, inductive reasoning, and overlay analysis to explore both theoretical and practical aspects of compatible marine utilization models. The paper begins by clarifying the logic of compatible sea use through marine functional zoning and identifying its core characteristics: quantity, spatial conflict, and impacts on natural attributes. Building on China’s national territorial spatial planning reforms and practical experiences, the paper introduces three major categories of compatible marine use models: development sequencing compatibility, spatial coexistence compatibility, and functional synergy compatibility. A compatibility discrimination matrix is developed to assess these models across different marine functional areas. Combined with the compatibility discrimination results, taking the marine and coastal spatial planning of Yantai City in China as a case study, the paper analyzes the compatibility demands and planning strategies within various marine functional areas. Finally, it evaluates the risks associated with each compatibility model and proposes targeted control strategies tailored to the specific features of each model and characteristics of sea use activities. The research findings highlight the positive role of compatible sea use models in promoting marine economic development, enhancing spatial efficiency, and mitigating sea use conflicts. However, these models also present varying potential risks, necessitating differentiated control strategies aligned with legal frameworks and specific sea use activities. The study offers valuable insights for MSP and contributes to the efficient utilization of marine resources and the advancement of marine spatial governance.

Evolutionary trajectory of TRPM2 channel activation by adenosine diphosphate ribose and calcium - Cheng Ma; Yanping Luo; Congyi Zhang; Cheng Cheng; Ning Hua; Xiaocao Liu; Jianan Wu; Luying Qin; Peilin Yu; Jianhong Luo; Fan Yang; Lin-Hua Jiang; et al. (Science Bulletin, 2024)

Design and numerical simulation of the elastomeric support for the topside modules of an FPSO - Yucu Huang; Yanping He; Yadong Liu; Ming Qiu; Mingzhi Li (Ocean Engineering, 2024)

Understanding the variability of ground-level ozone and fine particulate matter over the Tibetan plateau with data-driven approach - Haobin Zhong; Ling Zhen; Lin Yang; Chunshui Lin; Qiufang Yao; Yanping Xiao; Qi Xu; Jinsong Liu; Baihua Chen; Haiyan Ni; Wei Xu (Journal of Hazardous Materials, 2024)

The applicability of a SIF-based mechanistic model for estimating GPP at the canopy scale - Yanping Liu; Zhaoyong Hu; Genxu Wang; Arthur Gessler; Shouqin Sun (Agricultural and Forest Meteorology, 2024)

Condition-based maintenance method for multi-component systems under discrete-state condition: Subsea production system as a case - Rongkang Li; Baoping Cai; Yixin Zhao; Yiliu Liu; Yanping Zhang; Xiangdi Kong; Yonghong Liu (Ocean Engineering, 2024)

Enhanced ofloxacin degradation in water by a novel integrated photocatalysis and rotating magnetic field system - Ning Ding; Sijia Zhang; Jianxin Zhang; Yang Zhan; Bokang Wang; Hong Liu; Yanping Zhang; Yingxue Sun (Journal of Water Process Engineering, 2024)

Review of utilization of bamboo fiber in asphalt modification: Insights into preparation, performance, reinforcement, and challenges - Haibin Li; Songjiang Liu; Fan Yang; Siyu He; Hongjun Jing; Xiaolong Zou; Zhigang Li; Yanping Sheng (Journal of Cleaner Production, 2024)

Comparison of anaerobic co-digestion of vacuum toilet blackwater and kitchen waste under mesophilic and thermophilic conditions: Reactor performance, microbial response and metabolic pathway - Ziang Wang; Haixiang Li; Pingbo Wang; Jia Zhu; Ziyi Yang; Yanping Liu (Journal of Environmental Management, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

Leaf morpho-anatomy and taxonomic significance in five Dendrobium sect. Stachyobium species from China - Yunxi Xie; Yanping Wang; Lei Tao; Wenhao Liu; Yan Luo; Lu Li (Flora, 2024)

Potential modulation strategy on bismuth vanadate-based semiconductor to enhance antibiotic degradation in heterogeneous electro-Fenton system - Jinghui Pan; Zimu Zhang; Zuofang Yao; Songyu Fan; Tingting Zhu; Chenchen Xing; Yujia Liu; Jianhua Chen; Hongxiang Zhu; Yanping Hou; Shuangfei Wang (Chemical Engineering Journal, 2024)

Effect of Sulfate and Acid Orange 7 on Sb(V) Removal by Anaerobic Granular Sludge: Role of Granular Activated Carbon - Qi Li; Yanping Zhu; Yanbiao Liu; Xiaoguang Chen; Nan Jiang; Mengying Yan; Xuhua Li; Haoyu Xing; Yinzhou Bao; Manhong Huang (Water, Air, & Soil Pollution, 2024)

A highly sensitive SERS substrate of porous membrane-Ag NPs for kidney cancer detection - Sheng Chen; Jiamin Gao; Hongyi Zhang; Li Liu; Feng Lin; Zaijun Cheng; Yanping Chen; Dongyu Guo; Xingen Gao; Juqiang Lin (Analytica Chimica Acta, 2024)

Connotation analysis and path discussion of China’s land-sea coordination policy: based on the interregional externality theory - Yanping Li; Yuping Wang; Dahai Liu; Yuting Hou (Frontiers in Marine Science, 2024)
As two spatial geographic units that are both independent of each other and closely linked, the land and sea have complex spatial interactions. Therefore, China implements the land-sea coordination policy (LSC) needs to be approached from a more macroscopic, systematic and comprehensive perspective. Based on the interregional externality theory, this study takes the land-sea coordination policy of China as an example, and focuses on the interaction process and manifestation between land and sea, and then explores the connotation and realization path of LSC. Firstly, we delineated the spatial unit and analyzed the land-sea interactions (LSI) using Vensim software. Secondly, the characteristics and manifestations of LSI are summarized from the perspective of interregional externalities. Finally, this study elucidates the foundational concept of implementing LSC and further propose actionable pathways for promoting land and sea development in a coordinated way, aimed at offering supportive decision-making insights for achieving LSC within the broader framework of China’s territorial spatial planning. Initiating LSC implementation involves strategies such as source control, process management, and interaction interface optimization. Deepening LSC effectiveness entails strengthening positive interregional externalities while mitigating negative interregional externalities.

Prioritizing the multifaceted community and species uniqueness for the conservation of lacustrine fishes in the largest subtropical floodplain, China - Yang Liu; Yang Yan; Li Lin; Linlong Wang; Yanping Zhang; Bin Kang (Journal of Environmental Management, 2024)

Knocking out Selenium Binding Protein 1 Induces Depressive-Like Behavior in Mice - Yi Jia; Xin Zhang; Yongmei Wang; Yang Liu; Jie Dai; Liangliang Zhang; Xian Wu; Jie Zhang; Hongxi Xiang; Yanping Yang; Zhu Zeng; Yulian Chen (Biological Trace Element Research, 2024)

Loop PDE of viral capsid protein is involved in immune escape of the emerging novel variant infectious bursal disease virus - Guodong Wang; Nan Jiang; Hangbo Yu; Xinxin Niu; Mengmeng Huang; Yulong Zhang; Wenying Zhang; Jinze Han; Mengmeng Xu; Runhang Liu; Ziwen Wu; Jingzhe Han; et al. (Veterinary Microbiology, 2024)

Quantitative evaluation and mechanism analysis of soil chemical factors affecting rice yield in saline-sodic paddy fields - Baishun Liu; Lihua Huang; Xiaotong Jiang; Ying Liu; Guangzhi Huang; Can Yang; Yanping Liang; Jinghui Cai; Ge Zhu; Qianqian Kong (Science of The Total Environment, 2024)

Enhanced Sb(V) removal of sulfate-rich wastewater by anaerobic granular sludge assisted with Fe/C amendment - Qi Li; Yanping Zhu; Nan Jiang; Jun Li; Yanbiao Liu; Xiaoguang Chen; Xiaoyang Xu; Huangyingzi Wang; Yimeng Ma; Manhong Huang (Science of The Total Environment, 2024)

Research on leaching behavior of manganese and ammonia nitrogen in electrolytic manganese residue under oxalic acid/hydrogen peroxide system - Chenxin Sun; Yu Zhang; Yanping Yang; Qian Shang; Yunqiu Liu; Qianlin Chen (Journal of Water Process Engineering, 2024)

Electron transfer mediated photo-Fenton-like synergistic catalysis of Fe,Cu-doped MIL-101 coupled with Ag3PO4: Quantitative evaluation and DFT calculations - Xiaojuan Chen; Liang Yao; Song Xu; Juhua He; Ning Li; Jiaxin Li; Bin Liu; Yanping Zhu; Xin Chen; Hailong Wang; Runliang Zhu (Environmental Pollution, 2024)

Mitochondria targeting photoredox catalyst-induced pyroptosis for enhanced immunotherapy against hypoxic tumor cells - Yanping Wu; Qingsong Liu; Shumeng Li; Wenhao Yu; Huanhuan Fan; Shankun Yao; Weijiang He; Zijian Guo; Yuncong Chen (Chemical Engineering Journal, 2024)

Multifunctional Ac@ZIF-8/AgNPs nanoplatform with pH-responsive and ROS scavenging antibacterial properties promotes infected wound healing - Yipeng Pang; Maofang Zhao; Yuhan Xie; Yanping Wang; Yuxin You; Yongding Ke; Chaoyi Zhang; Xiaohan Chen; Yijia Yang; Chunlei Zhang; Xi Chen; Yi Liu; et al. (Chemical Engineering Journal, 2024)

Phytoplankton community responses to the combined effects of internal waves and anticyclonic eddies shed from the Kuroshio intrusion - Yanping Zhong; Xiaolin Bai; Edward A. Laws; Wenfang Lu; Zhida Huang; Wupeng Xiao; Jixin Chen; Lingqi Ma; Xin Liu; Bangqin Huang (Ocean Dynamics, 2024)

Characterization of a membrane Fcγ receptor in largemouth bass (Micropterus saloumoides) and its response to bacterial challenge - Jingya Wang; Jing Wu; Yanping Ma; Le Hao; Wen Huang; Zhenxing Liu; Yugu Li (Fish Physiology and Biochemistry, 2024)

SVEN_5003 is a Major Developmental Regulator in Streptomyces venezuelae - Yanping Zhu; Ting Lu; Hanlei Zhang; Meng Liu; Xiuhua Pang (Current Microbiology, 2024)

On the use of EST-SSR to analysis the genetic diversity of segetale rye from China - Yonghe Che; Yanping Yang; Lai Wei; Yunjie Yang; Xiaolei Wen; Juan Guo; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Cereal Research Communications, 2024)

Environmental fate and safety analysis of methoxyfenozide application to control litchi and longan pests - Yanping Liu; Xiaonan Wang; Siwei Wang (Environmental Science and Pollution Research, 2024)
Litchi and longan pests significantly affect crop yield and quality. Chemical prevention and control are very effective for production; therefore, it is crucial to study fate assessment and appropriate field efficacy before pesticide application on crops to appropriately assess the health and ecological risks linked with these agents. This study conducted Good Agricultural Practice (GAP) field trials and laboratory experiments to elucidate the dissipation, terminal residues, and efficacy of methoxyfenozide on litchi and longan in six locations throughout China. To detect methoxyfenozide residues on litchi and longan, a QuEChERS/UPLC-MS/MS-based method was designed. The initial methoxyfenozide levels in litchi and longan ranged from 2.21–2.86 to 0.83–0.95 mg kg −1 and indicated half-lives of 5.1–5.3 and 5.3–5.7 days, respectively. After 7 days of foliage treatment, the concentrations of terminal methoxyfenozide residue were 0.78–2.61 and 0.02–1.01 mg kg −1 , which were less than the established maximum residue limit for methoxyfenozide in litchi and longan. The chronic (acceptable daily intake = 0.0055–0.0331%) dietary intake risk analysis for methoxyfenozide in longan and litchi indicated acceptable concentrations of terminal residue for the general population. Methoxyfenozide in litchi and longan was readily degraded in first-order kinetics models, the degradation rate on longan was higher than that on litchi, and their dietary risks were negligible to consumers. Two hundred forty grams per liter of methoxyfenozide suspension concentrate (SC) represents a highly efficacious insecticidal dose to control litchi and longan pests and indicates a significant application potential as it is rapidly degraded and linked with reduced post-treatment residue levels.

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

Influence of organic sulfur gas-phase sulfation on the NH3-SCR activity of CeO2 catalyst: The competitive adsorption and conversion of CS2 and COS at a low hydrolysis temperature - Zhibo Xiong; Zhenchang Sun; Jiaxing Liu; Yanping Du; Yafei Zhu; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Fuel, 2024)

The feeding strategies of the antarctic lanternfish electrona antarctica (pisces: myctophidae) in the amundsen and cosmonaut seas (southern ocean), assessed with a classification tree analysis - Mi Duan; Chi Zhang; Yanping Luo; Libao Gao; Guankui Liu; Chunlin Liu; Yongming Sun; Jianchao Li; Shuyang Ma; Wenchao Zhang; Yongjun Tian (Polar Biology, 2024)

QTL mapping for agronomic traits in Agropyron Gaertn. CP population at the flowering stage - Yonghe Che; Jing Yang; Yutong He; Nan Song; Yanping Yang; Lai Wei; Xinming Yang; Yannong Zhang; Jinpeng Zhang; Haiming Han; Xiuquan Li; Shenghui Zhou; et al. (Euphytica, 2024)

Universal patterns and differences in graded aggressive calls of greater horseshoe bats from distant populations - Kangkang Zhang; Yanping Yu; Tong Liu; Jianan Ding; Hao Gu; Jiang Feng; Ying Liu (Animal Behaviour, 2024)

Controlled atmosphere storage alleviates the browning of walnut (Juglans regia L.) fruit through enhancing GABA-mediated energy metabolism - Niu Ye; Dongli Zhang; Shan Liu; Yongqi Zhang; Yifan Wang; Yan Tang; Xiangna Yang; Jiahao Chai; Yanping Ma; Huiling Ma (Postharvest Biology and Technology, 2024)

Vascular plant communities and biocrusts act as controlling factors in mitigating soil erosion on the Great Wall in a semi-humid area of Northwestern China - Yanping Liu; Rongliang Jia; Wanfu Wang; Yuchen Wan; Yanhong Gao; Hongtao Zhan; Jing Ren; Zhang Chen; Fei Qiu; Jing Zhu (Science of The Total Environment, 2024)

Understanding the spatial and seasonal variation of the ground-level ozone in Southeast China with an interpretable machine learning and multi-source remote sensing - Haobin Zhong; Ling Zhen; Qiufang Yao; Yanping Xiao; Jinsong Liu; Baihua Chen; Wei Xu (Science of The Total Environment, 2024)

Biochar co-pyrolyzed from peanut shells and maize straw improved soil biochemical properties, rice yield, and reduced cadmium mobilization and accumulation by rice: Biogeochemical investigations - Weijie Xu; Xiaocui Xie; Qi Li; Xing Yang; Jiajia Ren; Yanping Shi; Dan Liu; Sabry M. Shaheen; Jörg Rinklebe (Journal of Hazardous Materials, 2024)

Untangling the critical success factors of the latest compulsory waste sorting initiative in Shanghai: The role of accountability governance - Shenghao Xie; Yu Gong; Abraham Zhang; Yanping Liu; Changjun Li (Journal of Cleaner Production, 2024)

Effects of wastewater treatment plant effluent on microbial risks of pathogens and their antibiotic resistance in the receiving river - Zijian Xiao; Yuanyuan Qin; Li Han; Yifan Liu; Ziyi Wang; Yanping Huang; Yujing Ma; Yina Zou (Environmental Pollution, 2024)

Evaluating the environmental impact of agri-food waste reduction: A bibliographic analysis and conceptual framework - Haorui Wang; Na Luo; Yanping Liu; Yu Gong (Environmental Impact Assessment Review, 2024)

Rational design and fabricate of protonated crosslinked chitosan adsorbent for boosting the removal of nitrite in water - Wenbin Chen; Yanping Feng; Xiaoming Wang; Chenchen Zhang; Suyao Liu; Yibing Song; Yiwen Fang (Chemical Engineering Journal, 2024)

Online LC-ESI-MS/MS comparative analysis of N/O-glycopatterns in human colostrum from different ethnic groups in Northwest China - Xiaoqin Wang; Jing Liu; Shukai Wang; Yutao Xie; Yipei Liu; Jiangbo Fan; Yanping Li; Yu Lu; Linjuan Huang; Zhongfu Wang (Carbohydrate Polymers, 2024)

Detection of two homologous major QTLs and development of diagnostic molecular markers for sucrose content in peanut - Zhihui Wang; Yue Zhang; Dongxin Huai; Yuning Chen; Xin Wang; Yanping Kang; Liying Yan; Huifang Jiang; Kede Liu; Yong Lei; Boshou Liao (Theoretical and Applied Genetics, 2024)

Characterization of the Ovarian Development and Associated Factors during the Breeding Migration of Coilia nasus in the Yangtze River - Shuwei Wei; Zhong Hua; Yanping Yang; Fengjiao Ma; Wei Han; Wei Zhang; Congping Ying; Yanmin Deng; Kai Liu (Fishes, 2024)
Coilia nasus is a typical anadromous migratory fish found in the lower reaches of the Yangtze River. Every year, C. nasus clusters offshore and swims upstream along the Yangtze River into the tributaries and lakes in the middle and lower reaches of the Yangtze River to breed. In this study, female C. nasus were collected as study subjects from the Chongming section of Shanghai, the Taizhou section of Jiangsu, and the Anqing section of Anhui. Their ovaries were used to examine tissue sections and investigate gene expression, including the follicle-stimulating hormone receptor (fshr), the luteinizing hormone receptor (lhr), kisspeptin-1 (kiss1), and forkhead box l2 (foxl2), which are related to reproductive development, while the serum levels of estrogen (including estradiol, E2) and progestins (including 17α,20β-dihydroxy-4-pregenen-3-one, 17α,20β-DHP) were also analyzed. Our results showed that, first, the growth period of the oocytes was small in stage II of ovarian development, in which both E2 and 17α,20β-DHP levels and gene expression were low. Then, in stage III, the growth period of the oocytes became large, and the yolk granules and oil droplets began to appear. Simultaneously, E2 and the expression of kiss1 and foxl2 were significantly elevated. Finally, stage IV was the period of a large amount of accumulation of nutrients in the oocytes, and 17α,20β-DHP levels and the expression of fshr and lhr were significantly elevated. These results enrich the theoretical study of ovarian development in the natural population of C. nasus, supplementing the biological basis of C. nasus reproduction and scientifically supporting the study of C. nasus population ecology and resource conservation.

SlCNR regulates postharvest water loss and wax accumulation in tomato fruit and directly represses the transcription of very-long-chain (VLC) alkane biosynthesis-related genes SlCER1-2 and SlCER6 - Di Chen; Tingyu Wang; Hua Huang; Qiaoli Zhang; Xue Chen; Zongyan Sun; Yanping Song; Yuetong Yi; Chengxia Liu; Donald Grierson; Jiankang Cao; Daqi Fu; et al. (Postharvest Biology and Technology, 2024)

Study of the wet-towing transportation of an FPSO with elastomeric-supporting topside modules - Yucu Huang; Yanping He; Ming Qiu; Yadong Liu; Mingzhi Li (Ocean Engineering, 2024)

Niacin alleviates extracellular matrix deposition in ethanol + CCl4-induced liver fibrosis through the HSP90/JAK1/STAT3 axis - Yanping Fan; Meilan Xue; Tianhu Shan; Yixian Bai; Huaqi Zhang; Man Liu; Peng Wang; Xi Liang; Hui Liang (Food Bioscience, 2024)

Pretreatment greatly facilitates ethyl levulinate production from catalytic alcoholysis of Napier grass stem - Huai Liu; Yanping Kong; Weipeng Song; Rui Zhang; Junhua Zhang; Yong Sun; Lincai Peng (Chemical Engineering Journal, 2024)

A Novel N Self-Doped Porous Biochar Synthesized by KHCO3-Activated Chicken Feather for the Remediation of Tetracycline-Contaminated Water and Soil - Yu Deng; Jingfan Chen; Zhidan Xiao; Jiaying Liu; Jie Zhang; Bingqi Zhu; Xiaotong You; Fuquan Ni; Tianqi Ao; Yanping Tan (Water, Air, & Soil Pollution, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Exogenous Epigallocatechin-3-Gallate Alleviates Pesticide Phytotoxicity and Reduces Pesticide Residues by Stimulating Antioxidant Defense and Detoxification Pathways in Melon - Yaxian Wu; Golam Jalal Ahammed; Zhengzhen Li; Yameng Wang; Qianying Wang; Mingya Fang; Yanping Zhang; Haihe Liu; Xin Li (Journal of Plant Growth Regulation, 2024)

Consequences of excess urea application on photosynthetic characteristics and nitrogen metabolism of Robinia pseudoacacia seedlings - Yong Zhang; Rui Liu; Zhenshan Liu; Yanping Hu; Zhuyuan Xia; Bin Hu; Heinz Rennenberg (Chemosphere, 2024)

Sulfate availability drives the reductive transformation of schwertmannite by co-cultured iron- and sulfate-reducing bacteria - Changdong Ke; Yanping Deng; Siyu Zhang; Meihui Ren; Bingcheng Liu; Jingyi He; Renren Wu; Zhi Dang; Chuling Guo (Science of The Total Environment, 2024)

Synthesis of defective Ni-Mn layered double hydroxides nanosheets via alkali-assisted Mo doping for urea electro-oxidation - Ming Yang; Wanyu Ge; Zirui Liu; Qiang Yue; Jun Zhang; Yanping Lv; Hao Wu (Fuel, 2024)

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

Tungsten and oxygen dual vacancies regulation of the S-scheme ZnSe/ZnWO4 heterojunction with local polarization electric field for efficient CO2 photocatalytic reduction - Ting Liang; Zebin Yu; Yuejing Bin; Shiming Zhang; Jingwen Wei; Yujia Liu; Tingting Zhu; Songyu Fan; Yuxiang Shen; Shuangfei Wang; Yanping Hou (Chemical Engineering Journal, 2024)

Seismic response of a mid-story isolated structure considering SSI in mountainous areas under long-period earthquakes - Feng Wan; Shengwu Qin; Dewen Liu; Tiange Zhao; Yanping Zheng; Hang Shan; Zhiang Li; Fusong Peng; Jingran Xu; Min Lei (Earthquake Engineering and Engineering Vibration, 2024)

Testing a biocontrol agent consortium for suppression of tomato bacterial wilt through rhizosphere microecological regulation - Xuefang Zheng; Jieping Wang; Meichun Chen; Yanping Chen; Zheng Chen; MingKuang Wang; Bo Liu (Applied Soil Ecology, 2024)

Targeted degradation of naphthalene by peroxymonosulfate activation using molecularly imprinted biochar - Xueji You; Chaomeng Dai; Zeyu Wang; Yanping Duan; Jun Bo Zhang; Xiaoying Lai; Jiajun Hu; Jixiang Li; Maisideke Maimaitijiang; Yalei Zhang; Shuguang Liu; Rongbing Fu (Chemosphere, 2023)

Transfer of antibiotic resistance genes from soil to wheat: Role of host bacteria, impact on seed-derived bacteria, and affecting factors - Yanping Shen; Yibo Liu; Yutong Du; Xu Wang; Jiunian Guan; Xiaohui Jia; Fukai Xu; Ziwei Song; Hongjie Gao; Baiyu Zhang; Ping Guo (Science of The Total Environment, 2023)

Impact of facemask debris on marine diatoms: Physiology, surface properties, sinking rate, and copepod ingestion - Fengyuan Chen; Zhen Zhang; Yanping Li; Hao Jiang; Yanfei Zhou; Hongbin Liu; Ke Pan; Jie Ma (Science of The Total Environment, 2023)

Proportion of dead cells in phytoplankton modulates community structure - Peixuan Wang; Edward A. Laws; Xin Liu; Jixin Chen; Yanping Zhong; Chao Xu; Bangqin Huang (Progress in Oceanography, 2023)

Promotional effect of H2O introduction on the NH3-SCR activity of the gas-phase sulfated CeO2 catalyst by organic CS2+COS: Influence of H2O concentration - Jiaxing Liu; Yafei Zhu; Zhenchang Sun; Yanping Du; Zhibo Xiong; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Journal of Environmental Chemical Engineering, 2023)

Walnut green husk extract enhances the effect of chlorine dioxide on kernel quality and antioxidant properties of fresh-eating walnuts during their shelf life - Dongli Zhang; Niu Ye; Mingrui Li; Guoli Dai; Yanping Ma; Yifan Wang; Chaobin Liu; Huiling Ma (Food Chemistry, 2023)

Carcass meat quality, volatile compound profile, and gene expression in Tan sheep under different feeding regimes - Xingang Zhao; Shuxian Zuo; Yanping Guo; Can Zhang; Yuejun Wang; Sijia Peng; Ming Liu; Bing Wang; Hao Zhang; Hailing Luo (Food Bioscience, 2023)

A mother-son model for multi-objective non-invasive load monitoring - Huawei Mei; Yanping Liu; Wangbin Cao; Yang Yu (Energy and Buildings, 2023)

Enhanced nitrogen removal in the upgrading of municipal wastewater treatment plants by using zero-valent iron-modified biofilm carriers and clinoptilolite-modified biofilm carriers - Yanping Shi; Tao Liu; Xie Quan; Shuo Chen; Hongtao Yu; Wuzhe Quan (Chemical Engineering Journal, 2023)

Controlled synthesis of CuS with different morphology and pollution control of Hg0 in non-ferrous smelting flue gas - Jin Zhao; Xueqian Wu; Yanping Ma; Wei Liu; Zhen Li; Songjian Zhao (Fuel, 2023)

Efficient degradation of tetrabromobisphenol A using peroxymonosulfate oxidation activated by a novel nano-CuFe2O4@coconut shell biochar catalyst - Xinxin Li; Xujing Li; Chuang Song; Xiaojin Yang; Yanping Liu; Jia Zhu (Environmental Pollution, 2023)

Nanopore Structure and Multifractal Characteristics of Continental Shale Oil Reservoir: A Case Study from Ziliujing Shales in the Sichuan Basin - Youzhi Wang; Wei Li; Xiandong Wang; Zhiguo Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Lijuan Cheng; Xiaofei Fu (Journal of Marine Science and Engineering, 2023)
Thermal maturity of the shales from the Ziliujing Formation of the Jurassic age in the Sichuan Basin is in the hydrocarbon generation window, which makes it a candidate for shale oil and gas development. The meso- and macropore characteristics and heterogeneity of shales are important factors affecting the occurrence and development of oil and gas. However, the meso- and macropores of the Ziliujing shales have not been systematically studied. Thus, the mineral compositions and total organic carbon (TOC) of samples from this formation, as well as its pore structure, are analyzed by low-temperature N2 adsorption technique. Moreover, the heterogeneity of the pores was determined by multifractal analysis. The results show that the Ziliujing shales can be classified into three types according to the distributions of mineral compositions of carbonate and mixed and argillaceous shales. Results revealed that the smallest meso- and macropore volume (PV), the smallest specific surface area (SSA), and the largest average pore diameter (APD) occur in the carbonate shales. However, the largest PV and SSA and the smallest APD are observed in the argillaceous shales. The porosity of carbonate shales is mainly concentrated between 5 nm and 30 nm. Compared with carbonate shales, the porosity with pore sizes less than 30 nm of mixed and argillaceous shales shows a rapid increase. Furthermore, inorganic minerals are the main factors affecting the pore distributions, while TOC shows a weak effect. Herein, clay minerals significantly increase the mesopore volume and the pore number with a size of less than 30 nm. The Dq-q curves reveal that the meso- and macropore distributions of Ziliujing shales show multifractal behavior, but the multifractal characteristics of pores of various shales are distinctly different. The information dimension D1, the Hurst exponent H, and the width of the right side D0–D10 are key indicators to distinguish the local variations within the pore structure of different types of shales. The carbonate shales have the largest multifractal spectra width and the smallest D1 and H, while the opposite trend is found for the argillaceous shales. Clay minerals reduce the heterogeneity of the meso- and macropore distributions and increase the pore connectivity. Nevertheless, the carbonate minerals exhibit a reverse trend. Finally, it was found that TOC does not impact pore complexity as much. Collectively, this study supports our understanding of the occurrence of shale oil within various reservoir facies, thereby providing a guideline for future explorations in the Ziliujing Formation of the Jurassic age in the Sichuan Basin.

Microplastic aging alters the adsorption-desorption behaviors of sulfamethoxazole in marine animals: A study in simulated biological liquids - Jiaxuan Li; Yunxue Li; Bushra Maryam; Xiaochen Chen; Yanping Zong; Jianbo Tu; Pingping Zhang; Xianhua Liu (Marine Pollution Bulletin, 2023)

Insight into the plant-associated bacterial interactions: Role for plant arsenic extraction and carbon fixation - Yibo Liu; Baiyu Zhang; Ye Yao; Bo Wang; Yiqi Cao; Yanping Shen; Xiaohui Jia; Fukai Xu; Ziwei Song; Chengpeng Zhao; HongJie Gao; Ping Guo (Science of The Total Environment, 2023)

Manipulating critical memory periods to treat psychiatry disorders - Jiahui Deng; Xiao Lin; Yongbo Zheng; Sizhen Su; Xiaoxing Liu; Kai Yuan; Le Shi; Yanping Bao; Lin Lu (Science Bulletin, 2023)

Extraction of rubidium and cesium from oilfield brine by the two-step adsorption–flotation method - Dezhen Fang; Miao Lu; Yanping Wang; Liang Ma; Kexin Li; Haining Liu; Huifang Zhang; Guosheng Shi; Zhijian Wu; Xiushen Ye (Minerals Engineering, 2023)

Effective degradation of tetracycline by Pd/AG/ITO electrode: Electrode preparation, characterization, kinetics, degradation mechanism and toxicity assessment - Chen Shao; Jian Zhang; Yuqing Liu; Yuting Jiang; Yanping Jia; Guomin Li; Zhong Sun (Journal of Environmental Chemical Engineering, 2023)

Adding the third component with similar building blocks to regulate the miscibility of active layer enables high efficient ternary solar cells - Shichu Peng; Jinxin Luo; Peng Li; Liangang Xiao; Chongqing Yang; Yaocheng Jin; Ruiying Lin; Yanping Huo; Yi Liu; Yonggang Min (Chemical Engineering Journal, 2023)

ZIF-8-derived hollow carbon polyhedra with highly accessible single Mn-N6 sites as peroxymonosulfate activators for efficient sulfamethoxazole degradation - Yue Zhao; Rui Gao; He Wang; Yanping Sun; Xiaohui Zhan; Lei Chen; Junyan Liu; Huixiang Shi (Chemical Engineering Journal, 2023)

Performance of production of polyhydroxyalkanoates from food waste fermentation with Rhodopseudomonas palustris - Tingxing Dan; Huiyan Jing; Tian Shen; Jia Zhu; Yanping Liu (Bioresource Technology, 2023)

Biocrust and sand burial together promote annual herb community assembly in an arid sandy desert area - Yanhong Gao; Rongliang Jia; Yanping Liu; Yun Zhao; Yongshen Wu; Haotian Yang; Lichao Liu; Yulong Duan; Lina Zhao; Wanxue You (Plant and Soil, 2023)

Effectively synthesized functional Si-doped carbon dots with the applications in tyrosinase detection and lysosomal imaging - Chenfang Miao; Xin Zhou; Xiaoyang Huang; Jiyue Huang; Yanping Chen; Yuebin Liu; Xiaomu Hu; Lingjun Zeng; Shaohuang Weng; Huixing Chen (Analytica Chimica Acta, 2023)

Isotopic signatures unveil the lead sources and migration in surface mangrove sediments - Zhenghua Tao; Guogan Peng; Fengyuan Chen; Qingjun Guo; Rongfei Wei; Jingli Liu; Yanping Li; Hao Jiang; Yongyan Liao; Ke Pan (Science of The Total Environment, 2023)

The lysosome-mitochondrion crosstalk engaged in silver nanoparticles-disturbed mitochondrial homeostasis - Jia Liu; Zhendong Huang; Suhan Yin; Xinru Zhou; Yanping Jiang; Longquan Shao (Science of The Total Environment, 2023)

Barriers to compulsory waste sorting for a circular economy in China - Abraham Zhang; Shenghao Xie; Yu Gong; Changjun Li; Yanping Liu (Journal of Environmental Management, 2023)

Thermal hydraulic design and mass optimization of a 100-kWe S-CO2 cooled Mars-surface fission reactor system - Qi Xue; Pan Wu; Ming Liu; Jianqiang Shan; Yanping Huang (Annals of Nuclear Energy, 2023)

Multiple-Batch Digestion of Community Solid Waste with Recirculated Slurry as Inoculum: Performance and Microbial Community - Jingjing Tong; Chuang Song; Mei Song; Maomao Yuan; Dexun Zou; Xinxin Li; Xusheng Zheng; Yanping Liu (BioEnergy Research, 2023)

An evolving view on food viscosity regulating gastric emptying - Yangyi Jin; Peter J. Wilde; Yingying Hou; Yanping Wang; Jianzhong Han; Weilin Liu (Critical Reviews in Food Science and Nutrition, 2023)

Bridging the gap between artificial intelligence and mental health - Tangsheng Lu; Xiaoxing Liu; Jie Sun; Yanping Bao; Björn W. Schuller; Ying Han; Lin Lu (Science Bulletin, 2023)

Simulation and experimental research on hydrodynamic performance of fully attached submarine in the surface and near the surface modes - Minmin Zheng; Yadong Liu; Youjiang Wang; Yanping He (Ocean Engineering, 2023)

Comparison of yield prediction models and estimation of the relative importance of main agronomic traits affecting rice yield formation in saline-sodic paddy fields - Baishun Liu; Ying Liu; Guangzhi Huang; Xiaotong Jiang; Yanping Liang; Can Yang; Lihua Huang (European Journal of Agronomy, 2023)

Release of metal elements from clays during elution with EDTA: Insights into the side effects of washing contaminated sites - Xueji You; Chaomeng Dai; Shuguang Liu; Yanping Duan; Bo Tan; Yalei Zhang (Applied Clay Science, 2023)

Effects of freeze-thaw dynamics and microplastics on the distribution of antibiotic resistance genes in soil aggregates - Fukai Xu; Jiunian Guan; Yumei Zhou; Ziwei Song; Yanping Shen; Yibo Liu; Xiaohui Jia; Baiyu Zhang; Ping Guo (Chemosphere, 2023)

Associations between residential greenness and asthma and allergic rhinitis in children: A systematic review and meta-analysis - Wei Liu; Kailun Liu; Jiao Cai; Shuang Ma; Minghan Yang; Quan Yang; Yanping Yuan (Sustainable Cities and Society, 2023)

Kinetics and mechanisms of bacteria disinfection by performic acid in wastewater: In comparison with peracetic acid and sodium hypochlorite - Ning Ding; Ziwei Li; Lin Jiang; Hong Liu; Yanping Zhang; Yingxue Sun (Science of The Total Environment, 2023)

A spatiotemporal deconstruction-based approach for identifying flash drought expansion: Normalized Area-Time Accumulation curve - Ruiqi Chen; Yi Liu; Ye Zhu; Liliang Ren; Yanping Qu; Jason A. Otkin; Vijay P. Singh (Journal of Hydrology, 2023)

Effect of oligosaccharides as lyoprotectants on the stability of curcumin-loaded nanoliposomes during lyophilization - Hanyun Jiang; Yanping Wang; Xiankang Xu; Leiyu Deng; Lifang Feng; Jianzhong Han; Weilin Liu (Food Chemistry, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Relationships between Abyssal Redox Conditions and Rock Magnetic Properties of Surficial Sediments in the Western Pacific - Yanping Chen; Dong Xu; Huafeng Qin; Geng Liu; Yibing Li; Weiwei Chen; Liang Yi (Journal of Marine Science and Engineering, 2023)
Reconstructing changes in deep/bottom-water redox conditions are critical for understanding the role of the deep ocean in global carbon and metals cycling; nevertheless, the quantitative relationships between redox proxies and abyssal dissolved oxygen are poorly investigated. In this work, we studied the rock magnetic properties of surficial sediments in the western Pacific to investigate their relationship with regional redox conditions. Our results reveal a consistent sedimentary magnetic mineral assemblage in the western Pacific, dominated by pseudo-single-domain magnetite (Fe3O4), while the ratio of detrital and biogenic magnetite particles in different sites varies substantially. Detailed analyses identified two major magnetic-coercivity components, with modal coercivity values of 13.1 ± 1.6 mT and 54.7 ± 5.3 mT, respectively. All the magnetic parameters we measured, including both concentration-dependent and grainsize-dependent parameters, and the magnetic coercivities, are generally correlated to sedimentary redox conditions; however, the coercivities obtained by mathematical unmixing exhibit a stronger linkage, explaining about a quarter of variance of redox changes. Our findings confirm the potential of magnetic properties for tracing abyssal redox changes in the western Pacific, while the observed magnetic-redox relationships are complex and need further investigation.

Microscopic Analysis of Natural Fracture Properties in Organic-Rich Continental Shale Oil Reservoirs: A Case Study from the Lower Jurassic in the Sichuan Basin, China - Xuefeng Bai; Saipeng Huang; Xiandong Wang; Zhiguo Wang; Youzhi Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Xiaofei Fu; Lijuan Cheng; Likai Cui; et al. (Journal of Marine Science and Engineering, 2023)
Natural fractures are of paramount importance in storing carbon in shale oil reservoirs, where ultra-low porosity and permeability necessitate their essentiality for enhanced oil recovery. Therefore, comprehensively clarifying the characteristics of natural fractures in shale oil reservoirs is imperative. This paper focuses on investigating the microscopic features of natural fractures in organic-rich continental shale oil reservoirs that are commonly found in the Lower Jurassic strata of the Sichuan Basin, employing them as a representative example. Multiple methods were utilized, including mechanical testing, Kaiser testing, multi-scale CT scanning (at 2 mm, 25 mm, and 100 mm scales), and a numerical simulation of fluid seepage in fracture models. The results revealed that the in situ stress of the target seam displays the characteristic of σH > σv > σh, with σv and σh being particularly similar. The relatively high lateral stress coefficient (ranging from 1.020 to 1.037) indicates that the horizontal stresses are higher than the average level. Although the 2 mm CT scan provides a more detailed view of fractures and connected pores, it primarily exhibited more pore information due to the high resolution, which may not fully unveil additional information about the fractures. Thus, the 25 mm shale core is a better option for studying natural fractures. The tortuosity of the different fractures indicated that the morphology of larger fractures is more likely to remain stable, while small-scale fractures tend to exhibit diverse shapes. The simulations demonstrated that the stress sensitivity of fracture permeability is approximately comparable across different fracture scales. Therefore, our research can enhance the understanding of the properties of natural fractures, facilitate predicting favorable areas for shale oil exploration, and aid in evaluating the carbon storage potential of shale oil reservoirs.

Genetic Diversity and Population Structure Analysis of Chinese Mitten Crab (Eriocheir sinensis) in the Yangtze and Liaohe Rivers - Lin Zhou; Jiancao Gao; Yanping Yang; Zhijuan Nie; Kai Liu; Gangchun Xu (Fishes, 2023)
Recently, the economic traits of Chinese mitten crab (Eriocheir sinensis) varieties have had a negative tendency. Meanwhile, the status of wild germplasm resources of E. sinensis is unknown, hindering the utilization of wild germplasm resources and the green development of the E. sinensis industry. Thus, the conservation of the wild E. sinensis germplasm resource is of great significance. To this end, we collected wild E. sinensis from two different river basins, the Yangtze River basin, and the Liaohe River basin, and analyzed the genetic diversity as well as the genetic differentiation in E. sinensis populations. Based on eight microsatellite markers, we found moderate genetic diversity in E. sinensis populations regardless of river basin. Based on the mitochondrial D-loop region, we found that all populations are at mutation drift equilibrium, while the Nm between any two populations is greater than 1. We hypothesized the existence of island model gene flow patterns among E. sinensis. Interestingly, genetic differentiation among E. sinensis populations was low, except that between Liaohe and Anqing or Shanghai populations. Additionally, geometric morphological analysis could distinguish E. sinensis from different basins, with an accuracy of 94.2–100%. Given the similar genetic diversity in the two basins, the genetic convergence of E. sinensis from different basins deserves further attention.

Modeling EDTA-facilitated cadmium migration in high- and low-permeability systems using MODFLOW and RT3D - Xueji You; Shuguang Liu; Somayeh G. Esfahani; Yanping Duan; Jixiang Li; Chaomeng Dai; Charles J. Werth (Journal of Contaminant Hydrology, 2023)

Nitrogen doping excited Ru and Ti3C2−xNx support for hydrogen generation from ammonia borane - Licheng Liang; Linyan Bian; Yanping Fan; Shuyan Guan; Xianyun Liu; Qunying Sun; Baozhong Liu (Fuel, 2023)

Peroxymonosulfate activation by Ru/CeO2 for degradation of Triclosan: Efficacy, mechanisms and applicability in groundwater - Chaomeng Dai; Xueji You; Qian Liu; Yueming Han; Yanping Duan; Jiajun Hu; Jixiang Li; Zhi Li; Lang Zhou; Yalei Zhang; Shuguang Liu (Chemical Engineering Journal, 2023)

Effects of grazing exclusion on vegetation community characteristics over 22 years in the Zoige alpine meadows from China - Xue Jiang; Li He; Yanping Qu; Banghong Jian; Dongzhou Deng; Mei Liu; Jingtian Yang; Yunlong Ma; Dechao Chen; Yi Huang (Acta Oecologica, 2023)

Analysis and realization of the influence of sea ice flexural strength on ice resistance in numerical simulation of icebreaking by icebreaker - Zhe Chen; Yanping He; Yupei Ren; Yadong Liu (Ocean Engineering, 2023)

The effect of pH/PAC on the coagulation of anionic surfactant wastewater generated in the cosmetic production - Lanhe Zhang; Xiaolin Liu; Mingshuang Zhang; Tiezheng Wang; Hong Tang; Yanping Jia (Journal of Environmental Chemical Engineering, 2023)

Specific protection mechanism of oligosaccharides on liposomes during freeze-drying - Leiyu Deng; Yanping Wang; Hanyun Jiang; Xiankang Xu; Jianzhong Han; Weilin Liu (Food Research International, 2023)

A general way to manipulate electrical conductivity of graphene - Liqing Chen; Nian Li; Xinling Yu; Shudong Zhang; Cui Liu; Yanping Song; Zhao Li; Shuai Han; Wenbo Wang; Pengzhan Yang; Na Hong; Sarmad Ali; et al. (Chemical Engineering Journal, 2023)

An improved zigzag-type printed circuit heat exchanger for supercritical CO2 Brayton cycles - Shenghui Liu; Cheng Gao; Minyun Liu; Yunxuan Chen; Jia Tang; Yanping Huang; Xiaoliang Zhu; Tianyang Xing (Annals of Nuclear Energy, 2023)

China Brain Project: from bench to bedside - Xiaoxing Liu; Teng Gao; Tangsheng Lu; Yanping Bao; Gunter Schumann; Lin Lu (Science Bulletin, 2023)

Ca2+-dependent TaCCD1 cooperates with TaSAUR215 to enhance plasma membrane H+-ATPase activity and alkali stress tolerance by inhibiting PP2C-mediated dephosphorylation of TaHA2 in wheat - Minghan Cui; Yanping Li; Jianhang Li; Fengxiang Yin; Xiangyu Chen; Lumin Qin; Lin Wei; Guangmin Xia; Shuwei Liu (Molecular Plant, 2023)

Increasing β-carotene bioavailability and bioactivity in spinach demonstrated using excipient nanoemulsions—especially those of long-chain triglycerides - Xiaojuan Liu; Yanping Lin; Kangfei Yao; Junting Xie; Jie Xiao; Yong Cao (Food Chemistry, 2023)

A negative-response strain sensor towards wearable microclimate changes for body area sensing networks - Jing Liu; Junze Zhang; Zeyu Zhao; Yanping Liu; Wai Cheong Tam; Zhaozhu Zheng; Xiaoqin Wang; Yuling Li; Zekun Liu; Yi Li; Gang Li (Chemical Engineering Journal, 2023)

The development and future frontiers of global ecological restoration projects in the twenty-first century: a systematic review based on scientometrics - Xue Jiang; Yitao Sun; Yanping Qu; Houyuan Zeng; Jingtian Yang; Kaiyou Zhang; Lei Liu (Environmental Science and Pollution Research, 2023)

Removal of chlorine, microparticles and water from high-viscosity liquids by a sand filter coupling hydrocyclone - Aosong Wei; Jianping Li; Minjie Shan; Wenjie Lv; Jianqi Chen; Pengbo Fu; Yanping Liu; Weichun Xu; Li Dai; Hualin Wang (Process Safety and Environmental Protection, 2023)

Numerical analysis of continuous icebreaking performance of icebreakers with different bow types - Yupei Ren; Zhe Chen; Yanping He; Chao Chen; Yadong Liu; Guangyao Zheng (Ocean Engineering, 2023)

Doing more with less: How to design a good subgroup governance model for the air pollution transport network in “2+26” cities of China? - Wenxia Zeng; Xi Chen; Huizhong Dong; Yanping Liu (Journal of Environmental Management, 2023)

A magnetic adsorbent with metal-organic framework based on ammonium phosphomolybdenum heteropoly tungstate (AWP): Selective adsorption of Rb+ and Cs+ from aqueous resources and stripping with ammonium salts - Yanping Wang; Kexin Li; Liang Ma; Dezhen Fang; Miao Lu; Xiushen Ye; Haining Liu; Huifang Zhang; Xiaoli Tan; Zhijian Wu (Hydrometallurgy, 2023)

A mathematical model for phosphorus interactions and transport at the sediment-water interface in a large shallow lake - Yanping Wang; Zhaoliang Peng; Gang Liu; Hui Zhang; Xiangqian Zhou; Weiping Hu (Ecological Modelling, 2023)

One-step self-assembly of multilayer graphene oxide via streamlined click reactions for sensitive colorimetric assays - Yanfeng Gao; Yanping Wang; Xinli Liu; Zhenxing Zhu; Zhun Li; Zhibin Zhang; Yi Yin; William Chi Shing Cho; Yujun Song; Yuzhen Wang (Analytica Chimica Acta, 2023)

Genetic characteristics and growth patterns of the hybrid grouper derived from the hybridization of Epinephelus fuscoguttatus (female) × Epinephelus polyphekadion (male) - Liu Cao; Pan Chen; Xingrong Hou; Jun Ma; Ning Yang; Yanping Xu; Yanjin Zhang; Anqi Zhao; Jiyuan Zhang; Xinyu Li; Hai Huang (Journal of Fish Biology, 2023)
Hybridization is one of the primary methods used to cultivate farmed grouper species. The hybrid grouper derived from crossing Epinephelus fuscoguttatus (♀) and E. polyphekadion (♂) exhibits growth superiority over its parents. The genetic characteristics and growth patterns of the hybrid grouper have not yet been defined. This study confirms the ploidy level of the hybrid grouper (2 n = 48) using chromosome count analysis and flow cytometry. The 5S rDNA family was used to evaluate genetic diversity. Only one 5S class (~400 bp) was detected in the hybrid grouper, which could be used to distinguish between two different types based on nucleotide sequences, likely representing homologous unit classes from the female and male parental species. Growth patterns of 5–8‐month‐old hybrid groupers were also monitored. In this phase, a positive allometric growth pattern in body mass with total length was found. Body height and body mass were significantly correlated based on correlation and path coefficient, suggesting that body height could serve as an excellent index to increase body mass. These results aid our understanding of the genetic evolution of the hybrid grouper and inform the development of improved rearing techniques.

MnOx@N-doped carbon nanosheets derived from Mn-MOFs and g-C3N4 for peroxymonosulfate activation: Electron-rich Mn center induced by N doping - Yue Zhao; Xiaohui Zhan; Yanping Sun; He Wang; Lei Chen; Junyan Liu; Huixiang Shi (Chemosphere, 2023)

Eukaryotic community succession on discarded face masks in the marine environment - Jie Ma; Fengyuan Chen; Zhen Zhang; Yanping Li; Jingli Liu; Ciara Chun Chen; Ke Pan (Science of The Total Environment, 2023)

S-scheme MIL-101(Fe) octahedrons modified Bi2WO6 microspheres for photocatalytic decontamination of Cr(VI) and tetracycline hydrochloride: Synergistic insights, reaction pathways, and toxicity analysis - Shijie Li; Chunchun Wang; Yanping Liu; Yazi Liu; Mingjie Cai; Wei Zhao; Xiaoguang Duan (Chemical Engineering Journal, 2023)

Citric Acid and Poly-glutamic Acid Promote the Phytoextraction of Cadmium and Lead in Solanum nigrum L. Grown in Compound Cd–Pb Contaminated Soils - Yu Wang; Weidong Duan; Chao Lv; Zhuangzhuang Wei; Yanping Zhu; Qi Yang; Ying Liu; Zhenguo Shen; Yan Xia; Kun Duan; Lingtong Quan (Bulletin of Environmental Contamination and Toxicology, 2023)

Fcγ receptor‐mediated phagocytosis pathway was involved in phagocytosis of mIgM + B lymphocytes from largemouth bass ( Micropterus salmoides ) - Jing Wu; Yifan Nie; Jingya Wang; Guoqing Feng; Le Hao; Yanping Ma; Yugu Li; Zhenxing Liu (Journal of Fish Biology, 2023)
The potential for phagocytosis has been proven in teleost B cells, but the research on the regulatory mechanism of phagocytosis remains lacking. In this study, three largemouth bass ( Micropterus salmoides ) (15 ± 5 g) were injected intraperitoneally with Nocardia seriolae (10 5 CFU/100 μl/fish) in vivo , and their spleen was collected at 72 h post‐infection for mRNA‐seq. After the de novo assembly of the paired‐end reads, 73,622 unigenes were obtained. Gene expression profiling revealed that 2043 unigenes were differentially expressed after N. seriolae infection, comprising 1285 upregulated and 758 downregulated unigenes ( q ‐value 0.05, log2FC > |2|) of which 181 genes were involved in phagocytosis. The Kyoto Encyclopaedia of Genes and Genomes (KEGG) analysis demonstrated that 12 differentially expressed genes (DEG) associated with phagocytosis were enriched in the Fcγ receptor‐mediated phagocytosis signalling pathway. In vitro , the phagocytic ability of mIgM + B lymphocytes was validated using indirect immunofluorescence assay (IIFA) and fluorescence activating cell sorter (FACS), and the phagocytosis rates of the mIgM + B lymphocytes incubated with a Lyn inhibitor had decreased from 18.533 ± 6.00% to 11.610 ± 4.236% compared with the unblocked group. These results suggested that the Fcγ receptor‐mediated phagocytosis signalling pathway had participated in the phagocytosis of B cells and provide further insight into the role of B cells in innate immunology.

Enhanced silage pretreatment improving the biochemical methane potential of Miscanthus sinensis - Xinlei Huang; Meiying Ye; Lingli Yuan; Yanping Liu (Environmental Science and Pollution Research, 2022)

Ectopic expression of NAC transcription factor HaNAC3 from Haloxylon ammodendron increased abiotic stress resistance in tobacco - Xiashun Liu; Xingfeng Zong; Xia Wu; Hao Liu; Jvdong Han; Zhengpei Yao; Yanping Ren; Li Ma; Bo Wang; Hua Zhang (Planta, 2022)

Prevalence and risk factors of cardiovascular diseases and psychological distress among female scientists and technicians - Lijun Zhang; Yanping Bao; Guo Li; Shuhui Tao; Meiyan Liu (Journal of Zhejiang University-SCIENCE B, 2022)

Host adaptation of codon usage in SARS-CoV-2 from mammals indicates potential natural selection and viral fitness - Yanan Fu; Yanping Huang; Jingjing Rao; Feng Zeng; Ruiping Yang; Huabing Tan; Zhixin Liu; Weixing Du; Long Liu (Archives of Virology, 2022)

Simulation and risk assessment of typical antibiotics in the multi-media environment of the Yangtze River Estuary under tidal effect - Chaomeng Dai; Yueming Han; Yan Li; Yanping Duan; Shuguang Liu; Yalei Zhang; Yaojen Tu (Environmental Science and Pollution Research, 2022)

Genomic distribution of signal transducer and activator of transcription (STAT) family in colorectal cancer - Yanping Hu; Yifen Shen; Yang Zhao; Ying Tang; Chao Liu; Yongchun Gu; Tao Yang; Yihang Shen (Human Cell, 2022)

Impact of waste of COVID-19 protective equipment on the environment, animals and human health: a review - Sheng Yang; Yanping Cheng; Tong Liu; Shaoping Huang; Lihong Yin; Yuepu Pu; Geyu Liang (Environmental Chemistry Letters, 2022)

Responses of phytoplankton communities driven by differences of source water intrusions in the El Niño and La Niña events in the Taiwan Strait during the early spring - Yanping Zhong; Edward A. Laws; Jiafu Zhuang; Jingxiao Wang; Peixuan Wang; Caiyun Zhang; Xin Liu; Bangqin Huang (Frontiers in Marine Science, 2022)
The El Niño Southern Oscillation (ENSO) is one of the most important drivers of interannual variations of marine ecosystems, especially monsoonal ecosystems. The channel effect in a strait amplifies the impact of monsoons and may be an ideal area to study ecosystem responses to ENSO events. Previous studies have shown that physical processes in the Taiwan Strait (TWS) vary during the different ENSO phases, but the biological responses are still unclear. In this study, we found clear differences in the physical, chemical, and biological characteristics of the TWS between different ENSO phases based on data from satellites and field cruises during the 2015–2016 El Niño and 2017–2018 La Niña events. Although the monsoonal patterns were similar during early spring cruises during two ENSO events, the influence of the China Coastal Current (CCC), which is characterized by low sea surface temperature, low salinity, and high nutrient concentrations, was 1.5 times greater during the 2015–2016 El Niño than the 2017–2018 La Niña. The average chlorophyll a concentration was therefore higher in 2016 than that in 2018. The phytoplankton consisted mainly of diatoms, dinoflagellates, and cryptophytes during the 2015–2016 El Niño, but concentrations of those phytoplankton groups decreased, and concentrations of prasinophytes, Synechococcus , and Prochlorococcus increased during the 2017–2018 La Niña. Their influence of the CCC and warm currents were associated with the variations in phytoplankton community structure in the TWS. The results of this study enhance understanding of the responses of marine ecosystems to climate variabilities, and of the changes that climate change may bring to strait ecosystems.

Polyethylene microplastic exposure and concurrent effect with Aeromonas hydrophila infection on zebrafish - Ning Ding; Lin Jiang; Xiao Wang; Chun Wang; Yue Geng; Jianxin Zhang; Yingxue Sun; Yanping Zhang; Quan Yuan; Hong Liu (Environmental Science and Pollution Research, 2022)

Fungal dynamic changes in naturally fermented ‘Kyoho’ grape juice - Wenjuan Zhao; Zhiming Zhang; Yuhong Gao; Xiaozhen Liu; Chaojin Du; Fuxian Ma; Sujie Wang; Wanyuan Shi; Yanping Yang; Ruyou Deng; Hanyao Zhang (Archives of Microbiology, 2022)

An Updated Genome Assembly Improves Understanding of the Transcriptional Regulation of Coloration in Midas Cichlid - Yunyun Lv; Yanping Li; Yi Liu; Zhengyong Wen; Yexin Yang; Chuanjie Qin; Qiong Shi; Xidong Mu (Frontiers in Marine Science, 2022)
Midas cichlid ( Amphilophus citrinellus ), a popular aquarium fish, attracts extensive attention from worldwide biologists mainly due to its morphological polymorphism (dark versus gold). Continuous efforts have therefore been paid to address mechanisms of its coloration variants, while it is far away from the detailed illustration of a clear regulatory network. Some limits may come from the absence of a high-quality genome assembly and a relatively accurate gene set. In this study, we sequenced about 149 Gb of nucleotide sequences of Midas cichlid, generating a genome assembly with a total size of 933.5 Mb, which exhibits a good genome continuity with a contig N50 of 10.5 Mb. A total of 25,911 protein-coding genes were annotated and about 90% completeness was achieved, which helps to build a good gene pool for understanding expressional differences of color variation. With the assistance of the final gene set, we identified a total of 277 differential expressional genes (DEGs), of which 97 up- and 180 downregulated were determined in dark-vs-gold comparisons. Two protein-protein interaction (PPI) networks were constructed from these DEGs, and three key functional modules were classified. Hub genes within each module were evaluated, and we found that the third key module contains tyrp1b , oca2 , pmela , tyr , and slc24a5 , which were previously proven to be associated with melanin formation. Two downregulated DEGs ( myl1 and pgam2 ) in the first key module may be involved in muscle movement and spermatogenesis, implying that certain side effects could result from the morphological polymorphism. The first key module, consisting of proteins encoded by upregulated DEGs that were associated with MAPK signaling, Toll-like receptor signaling, and gonadotropin-releasing hormone pathways, may contribute to a negative upstream regulation or downstream influence on melanin biosynthesis. Taken together, our new genome assembly and gene annotation of Midas cichlid provide a high-quality genetic resource for biological studies on this species, and the newly identified key networks and hub genes in dark-vs-gold comparisons enhance our understanding of the transcriptional regulatory mechanisms underlying coloration changes not only in Midas cichlid but also in other fishes from freshwater to marine ecosystems.

Sequencing and comparative analysis of chloroplast genomes of three medicinal plants: Gentiana manshurica, G. scabra and G. triflora - Rong Zhao; Shuyue Yin; Jianing Xue; Chang Liu; Yanping Xing; Haibo Yin; Xue Ren; Jixiang Chen; Dingding Jia (Physiology and Molecular Biology of Plants, 2022)

Early-Holocene Paleo-Tropical Cyclone Activity Inferred from a Sedimentary Sequence in South Yellow Sea, East Asia - Geng Liu; Xibin Han; Yanping Chen; Jun Li; Lehui Song; Xin Zhou; Bangqi Hu; Liang Yi (Journal of Earth Science, 2022)

Detection of a major QTL and development of KASP markers for seed weight by combining QTL-seq, QTL-mapping and RNA-seq in peanut - Zhihui Wang; Liying Yan; Yuning Chen; Xin Wang; Dongxin Huai; Yanping Kang; Huifang Jiang; Kede Liu; Yong Lei; Boshou Liao (Theoretical and Applied Genetics, 2022)

X-ray Irradiation Improves Neurological Function Recovery of Injured Spinal Cord by Inhibiting Inflammation and Glial Scar Formation - Yi Wang; Yanping Niu; Fanguo Lin; Peng Su; Liesong Chen; Dong Liu; Yongming Sun (Journal of Molecular Neuroscience, 2022)

Biomonitoring and phytoremediation potential of the leaves, bark, and branch bark of street trees for heavy metal pollution in urban areas - Yanping Liu; Xiulian Zhao; Ruiming Liu; Jinxing Zhou; Zeping Jiang (Environmental Monitoring and Assessment, 2022)

Dopaminergic Neurons in the Ventral Tegmental–Prelimbic Pathway Promote the Emergence of Rats from Sevoflurane Anesthesia - Yanping Song; Ruitong Chu; Fuyang Cao; Yanfeng Wang; Yanhong Liu; Jiangbei Cao; Yongxin Guo; Weidong Mi; Li Tong (Neuroscience Bulletin, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Anisakidae parasitism activated immune response and induced liver fibrosis in wild anadromous Coilia nasus - Congping Ying; Xin Fang; Honglan Wang; Yanping Yang; Pao Xu; Kai Liu; Guojun Yin (Journal of Fish Biology, 2022)
Anisakidae nematode larvae is one of the most common parasites in wild anadromous Coilia nasus . This study aims to explore the mechanism of the C. nasus immune response to the parasitism of Anisakid nematode larvae. Results found that Anisakid nematode larvae parasitism caused liver injury as evidenced by histomorphology results as well as high levels of aminotransferase and aspertate aminotransferase. Furthermore, Anisakid nematode larvae parasitism induced an immune response in the host, which was characterized by the elevated populations of macrophages and neutrophils in the liver and head‐kidney in the Anisakidae‐infected group compared to the noninfected group. The expression of immunoglobulin IgM and IgD in the liver and head‐kidney was also increased in the Anisakidae‐infected group. The Anisakidae‐infected group showed higher activity of antioxidant enzymes catalase and superoxide dismutase, which indicates severe oxidative stress, and increased production of pro‐inflammatory cytokines, TNF‐α, IL‐6 as well as MCP‐1 in the liver compared with the noninfected group. As a result of inflammation, livers of hosts in the Anisakidae‐infected group showed fibrosis, and elevated expression of associated proteins including α‐smooth muscle actin, fibronectin, collagen type I and type III compared with the noninfected group. We demonstrated that Anisakid nematode larvae parasitism results in injury and fibrosis in the liver, and triggers immune cell infiltration and inflammation in the liver and head‐kidney of C. nasus . Altogether, the results provide a foundation for building an interaction between parasite and host, and will contribute to C. nasus population and fishery resource protection.

Thiamine induces resistance in tobacco against black shank - Tian Suohui; Chen Yanping; Zi Shuhui; Li Zhihua; Jin Honggang; Liu Jun; Liu Tao (Australasian Plant Pathology, 2022)

Fishery Status and Rebuilding of Major Economic Fishes in the Largest Freshwater Lake in China Based on Limited Data - Yang Liu; Huiyun Fu; Linlong Wang; Li Lin; Gang He; Peifeng Fu; Changlai Wang; Yanping Zhang; Bin Kang (Fishes, 2022)
Poyang Lake, the largest freshwater lake in China, possesses abundant fishery resources, but its fish stock status is still unclear. In this work, the stock status of and fishing efforts of nine major economic fishes in the Poyang Lake were estimated from 2000 to 2019 with a catch-based maximum sustainable yield (CMSY) model based on catch and resilience data. It was further predicted whether the biomass of those fishes could be restored to support maximum sustainable yield (Bmsy) under the policy of “Ten years fishing moratorium in the Yangtze River”. The results showed that goldfish Carassius auratus, grass carp Ctenopharyngodon idella, and black carp Mylopharyngodon piceus suffered from higher fishing efforts and low biomass in the past 20 years; bighead carp Hypophthalmichthys nobilis, yellow catfish Tachysurus fulvidraco, and common carp Cyprinus carpio responded differently to their fishing efforts; silver carp Hypophthalmichthys molitrix, Amur catfish Silurus asotus, and mandarin fish Siniperca chuatsi were underexploited. Six species were overfished in 2019, and their biomass would be expected to recover for sustainable exploitation during the fishing moratorium, except for M. piceus. This study provided a case study of feasible freshwater fishery evaluation in limnetic ecosystems.

Transport of TiO2 and CeO2 nanoparticles in saturated porous media in the presence of surfactants with environmentally relevant concentrations - Chaomeng Dai; Hui Shen; Yanping Duan; Xueji You; Xiaoying Lai; Shuguang Liu; Yalei Zhang; Leong Kah Hon; Kitae Baek; Yaojen Tu; Lang Zhou; Di Xu (Environmental Science and Pollution Research, 2022)

The expression and interaction proteins analysis of BjuFKF1/LKP2 in B. juncea - Jing Zeng; Anran Wu; Yuemin Yang; Liang Zhao; Li Chen; Chuanqi Wang; Xin Yang; Yanping Chen; Shiyan Liu; Pei Luo; Junli Wang (Molecular Genetics and Genomics, 2022)

Recombinant Avian β-Defensin Produced by Food-Grade Lactococcus as a Novel and Potent Immunological Enhancer Adjuvant for Avian Vaccine - Tingting Wang; Zhihao Wang; Jielan Mi; Wenqian Wang; Kai Li; Xiaole Qi; Yulong Gao; Li Gao; Changjun Liu; Yanping Zhang; Qing Pan; Xiaomei Wang; et al. (Probiotics and Antimicrobial Proteins, 2021)
In this study, we expressed rAvBD1-2–6-13 protein through Lactococcus lactis NZ3900, and the effects of the recombinant L. lactis NZ3900 as an immune enhancer and immune adjuvant were verified using in vivo and in vitro tests. In vitro tests revealed that recombinant L. lactis NZ3900 significantly activated the NF-κB signaling pathway and IRF signaling pathway in J774-Dual™ report cells and significantly increased the transcript levels of IL-10, IL-12p70, CD80, and CD86 in chicken PBMCs and chicken HD11 cells. In vivo experiments revealed that the immunized group supplemented with recombinant L. lactis NZ3900 as an adjuvant had significantly higher serum antibody titers and higher proliferative activity of PBMCs in the blood of the chickens immunized with NDV live and inactivated vaccines. Our study shows that the recombinant L. lactis NZ3900 has strong immunomodulatory activity both in vivo and in vitro and is a potential immune enhancer. Our work lays the foundation for the research and development of new animal immune enhancers for application in the poultry industry.

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

Magnetic minerals in Mid-Pleistocene sediments on the Caiwei Guyot, Northwest Pacific and their response to the Mid-Brunhes climate event - Liang Yi; Haifeng Wang; Geng Liu; Yanping Chen; Huiqiang Yao; Xiguang Deng (Acta Oceanologica Sinica, 2021)

The Innate Immune Response to Infection by Polyascus gregaria in the Male Chinese Mitten Crab (Eriocheir sinensis), Revealed by Proteomic Analysis - Yanping Yang; Fengjiao Ma; Juanjuan Dong; Lianxing Li; Ping Ren; Yuning Zhang; Yatao Wu; Yinping Wang; Kai Liu; Fang Zhang (Fishes, 2021)
The Chinese mitten crab (Eriocheir sinensis) is a representative catadromous invertebrate of the Yangtze River and a commercial species widely cultivated in China. Both cultivated and wild crabs suffer from a variety of parasites and pathogens, which can result in catastrophic economic losses in aquaculture revenue. Polyascus gregaria, a parasitic barnacle with a highly derived morphology, is specialized in invading these crabs. This study examines the immunological mechanism in E. sinensis infected with P. gregaria. Tandem mass tags (TMT), a specialized method of mass-spectrometry, was used to analyze the infection by P. gregaria resistance at the protein level. In the hepatopancreas of infected crabs, 598 proteins differentially expressed relating to physiological change, of which, 352 were upregulated and 246 were downregulated. Based on this differential protein expression, 104 GO terms and 13 KEGG pathways were significantly enriched. Differentially expressed proteins, such as ATG, cathepsin, serpin, iron-related protein, Rab family, integrin, and lectin, are associated with the lysosome GO term and the autophagy-animal KEGG pathways, both of which likely relate to the immune response to the parasitic P. gregaria infection. These results show the benefit of taking a detailed, protein-level approach to understanding the innate immune response of aquatic invertebrates to macroparasite infection.

In-situ Detection Method for Microplastics in Water by Polarized Light Scattering - Tong Liu; Shijun Yu; Xiaoshan Zhu; Ran Liao; Zepeng Zhuo; Yanping He; Hui Ma (Frontiers in Marine Science, 2021)
Microplastics (MPs) have become the widespread contaminants, which raises concerns on their ecological hazards. In-situ detection of MP in water bodies is essential for clear assessment of the ecological risks of MPs. The present study proposes a method based on polarized light scattering which measures the polarization parameters of the scattered light at 120° to detect MP in water. This method takes the advantage of in-situ measurement of the individual particles and the experimental setup in principle is used. By use of the measured polarization parameters equipped by machine learning, the standard polystyrene (PS) spheres, natural water sample, and lab-cultured microalgae are explicitly discriminated, and MP with different physical and chemical properties can be differentiated. It can also characterize the weathering of different MP and identify the specific type from multiple types of MP. This study explores the capability of the proposed method to detect the physical and chemical properties, weathering state and concentration of MP in water which promises the future application in water quality sensing and monitoring.

The Response Regulator MacR and its Potential in Improvement of Antibiotic Production in Streptomyces coelicolor - Meng Liu; Wenhao Xu; Yanping Zhu; Xiqing Cui; Xiuhua Pang (Current Microbiology, 2021)

Correction to: Dryline characteristics in North America’s historical and future climates - Lucia Scaff; Andreas F. Prein; Yanping Li; Adam J. Clark; Sebastian A. Krogh; Neil Taylor; Changhai Liu; Roy M. Rasmussen; Kyoko Ikeda; Zhenhua Li (Climate Dynamics, 2021)

Dryline characteristics in North America’s historical and future climates - Lucia Scaff; Andreas F. Prein; Yanping Li; Adam J. Clark; Sebastian A. Krogh; Neil Taylor; Changhai Liu; Roy M. Rasmussen; Kyoko Ikeda; Zhenhua Li (Climate Dynamics, 2021)

Molecular Cloning and Characterization of FAD6 Gene from Chia (Salvia hispanica L.) - Yufei Xue; Lejing Li; Xuemei Liu; Huanhuan Jiang; Yanping Zhao; Songzhen Wei; Na Lin; Yourong Chai (Biochemical Genetics, 2021)

Mechanisms, physiology, and recent research progress of gastric emptying - Weilin Liu; Yangyi Jin; Peter J. Wilde; Yingying Hou; Yanping Wang; Jianzhong Han (Critical Reviews in Food Science and Nutrition, 2021)

A semi-supervised learning method for hyperspectral imagery based on self-training and local-based affinity propagation - Haimiao Ge; Haizhu Pan; Liguo Wang; Cheng Li; Yanzhong Liu; Wenlong Zhu; Yanping Teng (International Journal of Remote Sensing, 2021)

Overexpression of KcNHX1 gene confers tolerance to multiple abiotic stresses in Arabidopsis thaliana - Yanqin Wang; Yuan Guo; Fen Li; Yanping Liu; Shuangxia Jin (Journal of Plant Research, 2021)

Characterization of a novel brain cell line from Jian carp (Cyprinus carpio var. Jian) - Ying Li; Yanping Ma; Le Hao; Jiangyao Ma; Zhiling Liang; Zhenxing Liu; Hao Ke; Yugu Li (Fish Physiology and Biochemistry, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Clinical features and prognostic factors of patients with COVID-19 in Henan Province, China - Qianqian Zhang; Zheng Wang; Yanping Lv; Jiang Zhao; Qiang Dang; Dongfeng Xu; Dongxiang Zhao; Haiyang Liu; Ziqi Wang; Xingru Zhao; Zhiwei Xu; Xiaoju Zhang (Human Cell, 2021)

Probiotic Potential and Wide-spectrum Antimicrobial Activity of Lactic Acid Bacteria Isolated from Infant Feces - Xing Wang; Weidong Wang; Haoxin Lv; Hua Zhang; Yuan Liu; Miao Zhang; Yanping Wang; Zhongfang Tan (Probiotics and Antimicrobial Proteins, 2021)

Contamination, distribution, and risk assessment of antibiotics in the urban surface water of the Pearl River in Guangzhou, South China - Chang Wang; Yanping Zhao; Shuang Liu; Qin Xiao; Weixin Liang; Yumei Song (Environmental Monitoring and Assessment, 2021)

Associations of Serum Selenium Levels in the First Trimester of Pregnancy with the Risk of Gestational Diabetes Mellitus and Preterm Birth: a Preliminary Cohort Study - Peng Ju Liu; Aimin Yao; Liangkun Ma; Xiao Yan Chen; Song Lin Yu; Yanping Liu; Yi Xuan Hou (Biological Trace Element Research, 2021)

Associations of TMPRSS6 Polymorphisms with Gestational Diabetes Mellitus in Chinese Han Pregnant Women: a Preliminary Cohort Study - Peng Ju Liu; Aimin Yao; Xiao Yan Chen; Yanping Liu; Liangkun Ma; Yi Xuan Hou (Biological Trace Element Research, 2021)

Molecular evolution and pathogenicity of chicken anemia virus isolates in China - Yue Li; Nana Yan; Yongqiang Wang; Aijing Liu; Changjun Liu; Xingge Lan; Bo Yang; Yulong Gao; Honglei Gao; Xiaole Qi; Hongyu Cui; Kai Li; et al. (Archives of Virology, 2021)

Unraveling yield-related traits with QTL analysis and dissection of QTL × environment interaction using a high-density bin map in rapeseed (Brassica napus. L) - Yanping Xie; Jinsong Xu; Gang Tian; Lingli Xie; Benbo Xu; Kede Liu; Xuekun Zhang (Euphytica, 2020)

Effects of EDTA on adsorption of Cd(II) and Pb(II) by soil minerals in low-permeability layers: batch experiments and microscopic characterization - Xueji You; Shuguang Liu; Chaomeng Dai; Guihui Zhong; Yanping Duan; Yiping Guo; Aleksei Nikolavich Makhinov; José Tavares Araruna Júnior; Yaojen Tu; Kah Hon Leong (Environmental Science and Pollution Research, 2020)

Retention of nitrogen and phosphorus in Lake Chaohu, China: implications for eutrophication management - Yanping Wang; Xiangzhen Kong; Zhaoliang Peng; Hui Zhang; Gang Liu; Weiping Hu; Xiangqian Zhou (Environmental Science and Pollution Research, 2020)

Comparative analysis of the gut microbiota of grass carp fed with chicken faeces - Famin Ke; Yanping Gao; Li Liu; Chun Zhang; Qin Wang; Xiaowei Gao (Environmental Science and Pollution Research, 2020)

Pseudorabies virus encephalitis in humans: a case series study - Siyuan Fan; Hongxun Yuan; Lei Liu; Hongfang Li; Shengnan Wang; Weili Zhao; Yihan Wu; Pei Wang; Yafang Hu; Jun Han; Yanli Lyu; Wuchao Zhang; et al. (Journal of NeuroVirology, 2020)

Simulating the convective precipitation diurnal cycle in North America’s current and future climate - Lucia Scaff; Andreas F. Prein; Yanping Li; Changhai Liu; Roy Rasmussen; Kyoko Ikeda (Climate Dynamics, 2020)

Bacillus amyloliquefaciens Ameliorates H2O2-Induced Oxidative Damage by Regulating Transporters, Tight Junctions, and Apoptosis Gene Expression in Cell Line IPEC-1 - Yanping Wu; Han Xu; Xuefang Cao; Rongrong Liu; Li Tang; Zhonghua Zeng; Weifen Li (Probiotics and Antimicrobial Proteins, 2020)

Cloning and functional analysis of the calreticulin gene from the scleractinian coral Galaxea astreata - Yuanjia Huang; Yanping Zhang; Huipai Peng; Jigui Yuan; Li Liu (Acta Oceanologica Sinica, 2020)

Silica colloids as non-carriers facilitate Pb2+ transport in saturated porous media under a weak adsorption condition: effects of Pb2+ concentrations - Chaomeng Dai; Hui Zhou; Xueji You; Yanping Duan; Yaojen Tu; Shuguang Liu; Feng Zhou; Leong Kah Hon (Environmental Science and Pollution Research, 2020)

Effects of Bacillus Subtilis-Zinc on Rats with Congenital Zinc Deficiency - Yanping Huang; Baowei Wang; Guodong Liu; Wenhua Ge; Mingai Zhang; Bin Yue; Min Kong (Biological Trace Element Research, 2020)

Levels of human cytomegalovirus miR-US25-1-5p and miR-UL112-3p in serum extracellular vesicles from infants with HCMV active infection are significantly correlated with liver damage - Jing Zhang; Yujing Huang; Qing Wang; Yanping Ma; Ying Qi; Zhongyang Liu; Jingui Deng; Qiang Ruan (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

LncRNA LINC00470 promotes proliferation through association with NF45/NF90 complex in hepatocellular carcinoma - Wenwei Huang; Juntao Liu; Jijun Yan; Zhengbin Huang; Xiongjie Zhang; Yanping Mao; Xiufang Huang (Human Cell, 2020)

TiO2 and SiO2 Nanoparticles Combined with Surfactants Mitigate the Toxicity of Cd2+ to Wheat Seedlings - Chaomeng Dai; Hui Shen; Yanping Duan; Shuguang Liu; Feng Zhou; Deli Wu; Guihui Zhong; Akbar Javadi; Yao-Jen Tu (Water, Air, & Soil Pollution, 2019)

Long-term variation of storm surge-associated waves in the Bohai Sea - Yanping Wang; Yongling Liu; Xinyan Mao; Yutao Chi; Wensheng Jiang (Journal of Oceanology and Limnology, 2019)

Digestive enzyme activity of the Japanese grenadier anchovy Coilia nasus during spawning migration: influence of the migration distance and the water temperature - Fengjiao Ma; Yanping Yang; Min Jiang; Denghua Yin; Kai Liu (Journal of Fish Biology, 2019)
In this study, we investigated the activity levels of two major digestive enzymes (pepsin and lipase) in the commercially important Japanese grenadier anchovy Coilia nasus during its upstream migration to analyse the digestive physiological responses to starvation and to analyse the influence of the water temperature on enzyme activity. Water temperature had a significant effect on pepsin activity, while long‐term starvation resulted in a significant decrease in pepsin activity. As starvation continued, however, a slight increase in pepsin activity between the Wuhu (440 river km) and Anqing (620 river km) regions may indicate that C. nasus had refeeding behaviour due to its large expenditure of energy reserves. In contrast, lipase activity was not significantly affected by the water temperature but the effect of fasting increased as much as 13% of lipase activity from the Chongming region (20 river km) to Anqing region, suggesting that the stored lipids of grenadier anchovy were mobilised to meet energy requirements of upstream migration activity and gonad development. Lipid mobilisation activated lipoprotein lipase (LPL; proteins with lipase activity) to hydrolyse triacylglycerides (TAG), which is the first step of lipid assimilation and obtained energy from fatty acids under fasting conditions. Therefore, the increased lipase activity is attributed mainly to the lipase that is involved in endogenous lipid hydrolysis. Grenadier anchovy appears to adapt to long‐term starvation during migration and the increased lipase activity may indicate a crucial effect on lipid metabolism. This study demonstrated that distinct alterations occur in pepsin and lipase activities during the spawning migration of grenadier anchovy due to exogenous nutrition and endogenous metabolism. Furthermore, it provides a basis for further research on the digestive physiology and energy metabolism in this species.

The Growth Rate, Immune Status, Duodenal Development, and Cecal Microbial Diversity of 24-Day-Old Offspring of SD Rats Received Bacillus subtilis-Cu or CuSO4 During Pregnancy and Lactation Periods - Guodong Liu; Baowei Wang; Yanping Huang; Kailing Li; Wenhua Ge; Mingai Zhang; Bin Yue; Min Kong (Biological Trace Element Research, 2019)

Beraprost sodium mitigates renal interstitial fibrosis through repairing renal microvessels - Shulin Li; Yanping Wang; Lu Chen; Zhuojun Wang; Guodong Liu; Bangjie Zuo; Caixia Liu; Dong Sun (Journal of Molecular Medicine, 2019)

The distribution of plants and seed dispersers in response to habitat fragmentation in an artificial island archipelago - Jiajia Liu; Ferry Slik; David A. Coomes; Richard T. Corlett; Yanping Wang; Maxwell Wilson; Guang Hu; Ping Ding; Mingjian Yu (Journal of Biogeography, 2019)
Aim Small, old‐growth forest fragments generally have more small‐seeded plants than large patches, due to the disappearance of large seed dispersing vertebrates. This pattern may differ for secondary forest fragments where differential migration ability rather than persistence of seed dispersers may be driving plant community assembly. In this study, we investigated the effect of habitat fragmentation on seed dispersers and plant community structure in regenerating forests. Location The Thousand Island Lake, China. Taxon Plants, birds and mammals. Methods We compiled diversity and abundance data for birds and mammals on islands in the Thousand Island Lake, China. We also surveyed the secondary plant communities and measured seed dispersal traits. Results Community‐weighted mean seed size of woody plants decreased with island size. This pattern was related to compositional difference of the dispersers. We found that mammal diversity and abundance was only weakly or not related to island size; whereas bird diversity and abundance increased strongly with island size. Density of bird‐dispersed plants was significantly positively related with island size. Since birds tend to disperse smaller seeds than mammals, the trend in seed size may have been a consequence of the shift in relative abundance of the two disperser guilds. Main Conclusions Differential responses of seed dispersers to habitat fragmentation may lead to pervasive shifts in the plant community structure of regenerating forest fragments. Our study highlights the importance of keeping large continuous forests in order to retain mammals and their dispersal capabilities.

Single-repeat R3 MYB transcription factors from Platanus acerifolia negatively regulate trichome formation in Arabidopsis - Yanping Zhang; Jiaqi Zhang; Changsheng Shao; Zhiru Bao; Guofeng Liu; Manzhu Bao (Planta, 2019)

Genetic diversity and pathogenicity dynamics of Magnaporthe oryzae in the Wuling Mountain area of China - Xin Xu; Wu Yang; Ke Tian; Jie Zheng; Xinqiong Liu; Kai Li; Wei Lu; Yanping Tan; Yonghua Qin; Chuntai Wang (European Journal of Plant Pathology, 2019)

Active Biomonitoring of Metals with Cultured Anodonta woodiana: A Case Study in the Taihu Lake, China - Xiubao Chen; Yanping Su; Hongbo Liu; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2019)

The BET bromodomain inhibitor i-BET151 impairs ovarian cancer metastasis and improves antitumor immunity - Ai Liu; Dianxia Fan; Yanping Wang (Cell and Tissue Research, 2018)

The complete chloroplast genome sequence of the wild Chinese chestnut (Castanea mollissima) - Lili Cheng; Wugang Huang; Yanping Lan; Qingchang Cao; Shuchai Su; Zhijun Zhou; Jinbao Wang; Jianling Liu; Guanglong Hu (Conservation Genetics Resources, 2018)

Soil dissimilatory nitrate reduction processes in the Spartina alterniflora invasion chronosequences of a coastal wetland of southeastern China: Dynamics and environmental implications - Dengzhou Gao; Xiaofei Li; Xianbiao Lin; Dianming Wu; Baoshi Jin; Yanping Huang; Min Liu; Xing Chen (Plant and Soil, 2017)

Mineral composition variation in the shells of freshwater mussel Anodonta woodiana at different growth stages - Xiubao Chen; Yanping Su; Hongbo Liu; Tao Jiang; Jian Yang (Invertebrate Reproduction & Development, 2017)

Continental-scale convection-permitting modeling of the current and future climate of North America - Changhai Liu; Kyoko Ikeda; Roy Rasmussen; Mike Barlage; Andrew J. Newman; Andreas F. Prein; Fei Chen; Liang Chen; Martyn Clark; Aiguo Dai; Jimy Dudhia; Trude Eidhammer; et al. (Climate Dynamics, 2017)

Bmi1 Regulates the Proliferation of Cochlear Supporting Cells Via the Canonical Wnt Signaling Pathway - Xiaoling Lu; Shan Sun; Jieyu Qi; Wenyan Li; Liman Liu; Yanping Zhang; Yan Chen; Shasha Zhang; Lei Wang; Dengshun Miao; Renjie Chai; Huawei Li (Molecular Neurobiology, 2017)

Salicylic acid-induced antioxidant protection against low temperature in cold-hardy winter wheat - Jing Yu; Jing Cang; Yanping Li; Ru Huang; Qiuwei Lu; Xiutian Wang; Lijie Liu; Qinghua Xu; Kejian Zhang (Acta Physiologiae Plantarum, 2016)

Preparation of highly purified timosaponin AIII from rhizoma anemarrhenae through an enzymatic method combined with preparative liquid chromatography - Lu Lu; Yanping Liu; Yue Ding; Jianwei Hou; Yong Zhang; Haiping Xue; Tong Zhang (Natural Product Research, 2016)

Genetic diversity of gliadin in Secale cereale subsp. segetale from Xinjiang, China - Yonghe Che; Ming Dai; Yanping Yang; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Genetic Resources and Crop Evolution, 2016)

Effects of Calcium and Magnesium Ions on Acute Copper Toxicity to Glochidia and Early Juveniles of the Chinese Pond Mussel Anodonta woodiana - Hongbo Liu; Xiubao Chen; Yanping Su; Ik Joon Kang; Xuchun Qiu; Yohei Shimasaki; Yuji Oshima; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2016)

Four SQUAMOSA PROMOTER BINDING PROTEIN-LIKE homologs from a basal eudicot tree (Platanus acerifolia) show diverse expression pattern and ability of inducing early flowering in Arabidopsis - Hongji Han; Guofeng Liu; Jiaqi Zhang; Sisi Zhang; Fangfang Cai; Zhiru Bao; Yanping Zhang; Manzhu Bao (Trees, 2016)

A single mutation in the PBC loop of VP2 is involved in the in vitro replication of infectious bursal disease virus - Xiaole Qi; Xiang Gao; Zhen Lu; Lizhou Zhang; Yongqiang Wang; Li Gao; Yulong Gao; Kai Li; Honglei Gao; Changjun Liu; Hongyu Cui; Yanping Zhang; et al. (Science China Life Sciences, 2016)

Human cytomegalovirus-encoded miR-US4-1 promotes cell apoptosis and benefits discharge of infectious virus particles by targeting QARS - Yaozhong Shao; Ying Qi; Yujing Huang; Zhongyang Liu; Yanping Ma; Xin Guo; Shujuan Jiang; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2016)

A cluster of 3′ coterminal transcripts from US12–US17 locus of human cytomegalovirus - Ying Lu; Yanping Ma; Zhongyang Liu; Liying Han; Shuang Gao; Bo Zheng; Chang Liu; Ying Qi; Zhengrong Sun; Yujing Huang; Qiang Ruan (Virus Genes, 2016)

Particle-Associated Ambient Benzo[a]pyrene and Levels of Urinary 1-Hydroxypyrene in a Non-occupationally Exposed Population of Adults and Children in Lanzhou, China - Yunjiang Yu; Qiong Wang; Liangzhong Li; Zien Liu; Peng Sun; Yanping Zhang; Haipeng Lin; Mingdeng Xiang; Hui Li; Bigui Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Applications of Savitzky-Golay Filter for Seismic Random Noise Reduction - Yanping Liu; Bo Dang; Yue Li; Hongbo Lin; Haitao Ma (Acta Geophysica, 2016)

QTL mapping for flowering time in different latitude in soybean - Sijia Lu; Ying Li; Jialin Wang; Peerasak Srinives; Haiyang Nan; Dong Cao; Yanping Wang; Jinliang Li; Xiaoming Li; Chao Fang; Xinyi Shi; Xiaohui Yuan; et al. (Euphytica, 2015)

Genomic organization of a novel victorivirus from the rice blast fungus Magnaporthe oryzae - Lihua Tang; Yanping Hu; Lijiang Liu; Songsong Wu; Jiatao Xie; Jiasen Cheng; Yanping Fu; Guoming Zhang; Juntao Ma; Yongli Wang; Liyan Zhang (Archives of Virology, 2015)

Human cytomegalovirus miR-UL36-5p inhibits apoptosis via downregulation of adenine nucleotide translocator 3 in cultured cells - Xin Guo; Yujing Huang; Ying Qi; Zhongyang Liu; Yanping Ma; Yaozhong Shao; Shujuan Jiang; Zhengrong Sun; Qiang Ruan (Archives of Virology, 2015)

Effect of amino acid sequence variations at position 149 on the fusogenic activity of the subtype B avian metapneumovirus fusion protein - Bingling Yun; Yanni Gao; Yongzhen Liu; Xiaolu Guan; Yongqiang Wang; Xiaole Qi; Honglei Gao; Changjun Liu; Hongyu Cui; Yanping Zhang; Yulong Gao; Xiaomei Wang (Archives of Virology, 2015)

Morphological development and growth of the freshwater mussel Anodonta woodiana from early juvenile to adult - Xiubao Chen; Hongbo Liu; Yanping Su; Jian Yang (Invertebrate Reproduction & Development, 2015)

Effects of active, passive, and combined smoking on cervical cancer mortality: a nationwide proportional mortality study in Chinese urban women - Jingmei Jiang; Haiyu Pang; Boqi Liu; Philip C. Nasca; Biao Zhang; Yanping Wu; Wei Han; Margaret Gates; Tao Lu; Xiaonong Zou; Fang Xue; Lei Hou; et al. (Cancer Causes & Control, 2015)

Antagonism of miRNA-21 Sensitizes Human Gastric Cancer Cells to Paclitaxel - Bo Jin; Yanping Liu; Haijiang Wang (Cell Biochemistry and Biophysics, 2015)

Extracellular ATP is involved in the initiation of pollen germination and tube growth in Picea meyeri - Junhui Zhou; Chengyu Fan; Kai Liu; Yanping Jing (Trees, 2015)

Erratum to: Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Exploring the Wnt Pathway-Associated LncRNAs and Genes Involved in Pancreatic Carcinogenesis Driven by Tp53 Mutation - Qi Wang; He Jiang; Chen Ping; Ruizhe Shen; Tingting Liu; Juanjuan Li; Yuting Qian; Yanping Tang; Shidan Cheng; Weiyan Yao; Lifu Wang (Pharmaceutical Research, 2015)

Erythropoietin (EPO) Protects Against High Glucose-Induced Apoptosis in Retinal Ganglional Cells - Yunxiao Wang; Hui Zhang; Yanping Liu; Ping Li; Zhihong Cao; Yu Cao (Cell Biochemistry and Biophysics, 2015)

Intake of fruit and vegetables and risk of bladder cancer: a dose–response meta-analysis of observational studies - Baodong Yao; Yujie Yan; Xianwu Ye; Hong Fang; Huilin Xu; Yinan Liu; Sheran Li; Yanping Zhao (Cancer Causes & Control, 2014)

Molecular characterization of PXR and two sulfotransferases and hepatic transcripts of PXR, two sulfotransferases and CYP3A responsive to bisphenol A in rare minnow Gobiocypris rarus - Jiancao Gao; Yingying Zhang; Yanping Yang; Cong Yuan; Fang Qin; Shaozhen Liu; Yao Zheng; Zaizhao Wang (Molecular Biology Reports, 2014)

Effects of hydrogen peroxide accumulation, lipid peroxidation, and polyphenol oxidation during superficial scald development in ‘Fuji’ apples - Xingang Lu; Yanping Ma; Xinghua Liu (Horticulture, Environment, and Biotechnology, 2014)

Physical-Chemical Properties of Collagens from Skin, Scale, and Bone of Grass Carp ( Ctenopharyngodon idellus ) - Haibo Wang; Yanping Liang; Haiyin Wang; Hanjun Zhang; Min Wang; Liangzhong Liu (Journal of Aquatic Food Product Technology, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Dissipation, residues, and risk assessment of spirodiclofen in citrus - Haibin Sun; Congyun Liu; Siwei Wang; Yanping Liu; Mingjin Liu (Environmental Monitoring and Assessment, 2013)

Dopamine transporter availability in heroin-dependent subjects and controls: longitudinal changes during abstinence and the effects of Jitai tablets treatment - Ying Liu; Mei Han; Xingdang Liu; Yanping Deng; Yu Li; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Jinlong Gao (Psychopharmacology, 2013)

Impact of biochar application on nitrogen nutrition of rice, greenhouse-gas emissions and soil organic carbon dynamics in two paddy soils of China - Zubin Xie; Yanping Xu; Gang Liu; Qi Liu; Jianguo Zhu; Cong Tu; James E. Amonette; Georg Cadisch; Jean W. H. Yong; Shuijin Hu (Plant and Soil, 2013)

Growth and yield of oleic sunflower (Helianthus annuus L.) under drip irrigation in very strongly saline soils - Shuqin Wan; Yanping Jiao; Yaohu Kang; Shufang Jiang; Junli Tan; Wei Liu; Jing Meng (Irrigation Science, 2013)

Dissipation and residue of azoxystrobin in banana under field condition - Siwei Wang; Haibin Sun; Yanping Liu (Environmental Monitoring and Assessment, 2013)

Dissipation and Residue of Spinosad in Zucchini Under Field Conditions - Yanping Liu; Haibin Sun; Siwei Wang (Bulletin of Environmental Contamination and Toxicology, 2013)

Associations Between EEG Beta Power Abnormality and Diagnosis in Cognitive Impairment Post Cerebral Infarcts - Yanping Wang; Xiaoling Zhang; Junjun Huang; Minchu Zhu; Qiaobing Guan; Chunfeng Liu (Journal of Molecular Neuroscience, 2013)

Expression of biologically active human interferon alpha 2b in the milk of transgenic mice - Hui Li; Qingyou Liu; Kuiqing Cui; Jinfeng Liu; Yanping Ren; Deshun Shi (Transgenic Research, 2013)

Metals and Metalloids in the Water–Bloom-Forming Cyanobacteria and Ambient Water from Nanquan Coast of Taihu Lake, China - Yanping Su; Hongbo Liu; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2012)

Reference gene selection for qPCR in Ammopiptanthus mongolicus under abiotic stresses and expression analysis of seven ROS-scavenging enzyme genes - Jing Shi; Meiqin Liu; Junna Shi; Guangshun Zheng; Yanping Wang; Jinyu Wang; Yuzhen Chen; Cunfu Lu; Weilun Yin (Plant Cell Reports, 2012)

Dissipation and Residue of Myclobutanil in Lychee - Yanping Liu; Haibin Sun; Fengmao Liu; Siwei Wang (Bulletin of Environmental Contamination and Toxicology, 2012)

Inactivation of the extracytoplasmic function sigma factor Sig6 stimulates avermectin production in Streptomyces avermitilis - Libin Jiang; Yanping Liu; Pan Wang; Ying Wen; Yuan Song; Zhi Chen; Jilun Li (Biotechnology Letters, 2011)

Lin-28 reactivation is required for let-7 repression and proliferation in human small cell lung cancer cells - Lin Pan; Zhaohui Gong; Zhiwei Zhong; Zhuo Dong; Qiong Liu; Yanping Le; Junming Guo (Molecular and Cellular Biochemistry, 2011)

Effects of temporarily disrupting BBB on activity-induced manganese-dependent functional MRI - Zhiqiang Fa; Run Zhang; Peng Li; Jing Zhang; Peng Zhang; Shaofang Zhu; Qu Wu; Fanheng Huang; Yanping Liu; Lujun Yang; Haigang Chang; Zhibo Wen; et al. (Brain Imaging and Behavior, 2011)

Spatial and temporal variations of macro- and mesozooplankton community in the Huanghai Sea (Yellow Sea) and East China Sea in summer and winter - Hongju Chen; Yanping Qi; Guangxing Liu (Acta Oceanologica Sinica, 2011)

CO2 mitigation potential in farmland of China by altering current organic matter amendment pattern - ZuBin Xie; Gang Liu; QiCheng Bei; HaoYe Tang; JinShan Liu; HuiFeng Sun; YanPing Xu; JianGuo Zhu; Georg Cadisch (Science China Earth Sciences, 2010)

Caveolin-1 restoration by cholesterol enhances the inhibitory effect of simvastatin on arginine vasopressin-induced cardiac fibroblasts proliferation - Shaowei Liu; Yanping He; Yufeng Dou; Haichang Wang; Ling Tao; Lianyou Zhao; Fujun Shang; Hui Liu (Molecular and Cellular Biochemistry, 2009)

Diagnostic value of HCMV pp65 antigen detection by FCA for symptomatic and asymptomatic infection: compared to quantification of HCMV DNA and detection of IgM antibody in infants - Zhengrong Sun; Xiangshi Ceng; Zhiqin Mao; Jidong Wang; Qing Liu; Yaohua Ji; Yanping Ma; Ying Qi; Rong He; Qiang Ruan (Medical Microbiology and Immunology, 2009)

Endothelial cytoskeletal elements are critical for flow-mediated dilation in human coronary arterioles - Yanping Liu; Hongwei Li; Aaron H. Bubolz; David X. Zhang; David D. Gutterman (Medical & Biological Engineering & Computing, 2008)

Impacts of climatic factors on runoff coefficients in source regions of the Huanghe River - Liqun Chen; Changming Liu; Yanping Li; Guoqiang Wang (Chinese Geographical Science, 2007)

Effective induction of immune tolerance by portal venous infusion with IL-10 gene-modified immature dendritic cells leading to prolongation of allograft survival - Ming Zhang; Quanxing Wang; Yushan Liu; Yanping Sun; Guoshan Ding; Zhiren Fu; Zhilian Min; Youhua Zhu; Xuetao Cao (Journal of Molecular Medicine, 2004)